Polyethylene resin composition
By optimizing the composition and polymerization conditions of polyethylene resin, a polyethylene resin composition with excellent stretchability, mechanical properties and transparency was developed, which solved the shortcomings of existing polyethylene resins in these aspects and is suitable for high-performance biaxial applications. Manufacturing of stretch film.
Patent Information
- Application Number
- CN202480002535.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-01
- Filing Date
- 2024-04-02
- Publication Date
- 2025-01-17
AI Technical Summary
The existing polyethylene resins have shortcomings in mechanical properties, heat resistance and transparency, and it is difficult to meet the needs of high tensile and biaxial tensile films.
Developing a polyethylene resin composition consisting of an optimized first polyethylene and second polyolefin copolymer using a Ziegler-Natta catalyst by controlling the melt index, density, molecular weight distribution and crystallinity Polymerization is carried out with metallocene catalysts to ensure bimodal molecular weight distribution and excellent mechanical properties of the composition.
The polyethylene resin composition achieves excellent stretchability, mechanical properties and transparency, is suitable for manufacturing high-performance biaxially stretched films, and improves the hardness and heat resistance of the film.
Smart Images

Figure CN119325490A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0063112 filed on May 16, 2023, and Korean Patent Application No. 10-2024-0044221 filed on April 1, 2024, both of which are incorporated herein by reference in their entirety. Technical Field
[0003] The present disclosure relates to a polyethylene resin composition having excellent stretchability, mechanical properties, and transparency. Background Art
[0004] Conventional multilayer film packaging materials use composite materials mixed with polyamide (PA), polyethylene terephthalate (PET), polypropylene (PP), etc. However, with the recent increase in consumer interest in environmental issues, more easily recyclable single-material packaging is gaining attention. Therefore, there is a trend in the food packaging and distribution industry to use only polyethylene (PE), a common material, to manufacture "all PE" films.
[0005] However, polyethylene has disadvantages such as lower heat resistance, hardness, and transparency compared to resins such as polypropylene and polyethylene terephthalate.
[0006] To solve this problem, the development of technology to improve mechanical properties by manufacturing uniaxial or biaxially stretched films by blow molding or casting is being actively carried out. In order to apply this technology, polyethylene must have excellent stretchability and mechanical properties, and at the same time have appropriate transparency.
[0007] Therefore, there is a need to develop a polyethylene resin composition having excellent stretchability, mechanical properties and transparency. Summary of the invention
[0008] Technical issues
[0009] In order to solve the problems of the prior art, a polyethylene resin composition having excellent stretchability, mechanical properties and transparency is provided.
[0010] In addition, provided is a film having excellent stretchability, mechanical properties, and transparency, which is produced using the polyethylene resin composition.
[0011] Technical Solution
[0012] In order to solve the above problems, a polyethylene resin composition is provided, which satisfies the following conditions (a1) to (a5):
[0013] (a1)MI 2.16(ASTM D1238, 190°C, 2.16kg): 0.5 g / 10 min to 3.0 g / 10 min
[0014] (a2) Density (ASTM D792): 0.940 g / cm 3 Up to 0.955g / cm 3
[0015] (a3) MFRR(MI 21.6 / MI 2.16 ): 60 or more and less than 80
[0016] (a4) Molecular weight distribution (Mw / Mn): 10 to 14
[0017] (a5) In a temperature rising elution fractionation (TREF) analysis, based on the total weight of all eluted fractions,
[0018] Content of the polymer fraction eluted in the range of 25°C to 90°C: 20 wt% to 50 wt%, and
[0019] Content of the polymer fraction eluted in the range of 90°C to 120°C: 50 wt% to 80 wt%.
[0020] In addition, a method for preparing a polyethylene resin composition is provided, comprising:
[0021] The first step is to carry out a primary polymerization reaction of the ethylene in a first reactor in the presence of a Ziegler-Natta catalyst, transfer the obtained polymerization product to a second reactor, and add one or more ethylene monomers and C4-C8 alpha olefin monomers to carry out a secondary polymerization reaction to prepare a first polyethylene;
[0022] The second step is to produce a second polyethylene by polymerizing an ethylene monomer and a C4-C8 α-olefin monomer in the presence of a catalyst in a separate single reactor while introducing hydrogen, wherein the catalyst comprises a metallocene compound represented by the following Chemical Formula 1; and
[0023] The third step is to mix the first polyethylene and the second polyethylene in a weight ratio of 90:10 to 70:30;
[0024] [Chemical formula 1]
[0025]
[0026] In Chemical Formula 1,
[0027] B is boron,
[0028] M is a Group 4 transition metal,
[0029] R1 to R4 are each independently hydrogen, C 1-20 Alkyl, C 3-20 Cycloalkyl or C 6-20 Aryl, or R1 and R2, or R3 and R4 are connected to each other to form a substituted or unsubstituted C 6-60 Aromatic rings,
[0030] R5 and R6 are each independently C 1-20 Alkyl, C 3-20 Cycloalkyl or C 6-20 Aryl, or R5 and R6 are connected to each other to form a C 3-60 Alicyclic or C 6-60 Aromatic rings,
[0031] X1 and X2 are each independently C 1-20 Alkyl or -O(CO)R', where R' is C 1-20 alkyl,
[0032] Q is substituted or unsubstituted C 2-60 a heterocyclic ring comprising at least one selected from the group consisting of N, O and S,
[0033] Y and Y' are the elements that make up Q,
[0034] Y is N, O or S, and
[0035] Y' is an element of Q adjacent to Y and is N or C.
[0036] In addition, a film is provided, specifically a stretched film comprising the polyethylene resin composition.
[0037] Beneficial Effects
[0038] According to the present disclosure, provided are a polyethylene resin composition exhibiting excellent stretchability, mechanical properties, and transparency, and a film manufactured using the composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a graph showing the results of temperature rising elution fractionation (TREF) analysis of the polyethylene resin compositions of Examples 5 and 6 and Comparative Examples 10 and 14. DETAILED DESCRIPTION
[0040] In the present disclosure, the terms “first”, “second”, etc. are used to describe various components, and these terms are only used to distinguish specific components from other components.
[0041] The terms used herein are only used for the purpose of describing specific embodiments and are not intended to limit the present invention. Unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. It should be further understood that when the terms "comprise", "have" or "include" are used in this specification, it is to specify the presence of the features, quantities, steps, components or combinations thereof, but does not exclude the presence or addition of one or more other features, quantities, steps, components or combinations thereof.
[0042] Furthermore, "polyethylene" or "ethylene (co)polymer" is a concept including an ethylene homopolymer and / or a copolymer of ethylene and an α-olefin.
[0043] Since the present invention can be modified differently and have various forms, its specific embodiments are shown and described in detail by way of example. However, it is not intended to limit the present invention to the specific form disclosed, and it should be understood that the present invention includes all modifications, equivalents and substitutions within the concept and technical scope of the present invention.
[0044] The polyethylene resin composition of the present invention is described in detail below.
[0045] The polyethylene resin composition of the present disclosure may exhibit excellent stretchability, mechanical properties, and transparency by controlling melt index, density, weight average molecular weight (Mw), and content according to crystallinity.
[0046] Specifically, the polyethylene resin composition satisfies the following conditions (a1) to (a5):
[0047] (a1)MI 2.16 (ASTM D1238, 190°C, 2.16kg): 0.5 g / 10 min to 3.0 g / 10 min
[0048] (a2) Density (ASTM D792): 0.940 g / cm 3 Up to 0.955g / cm 3
[0049] (a3) MFRR(MI 21.6 / MI 2.16 ): 60 or more and less than 80
[0050] (a4) Molecular weight distribution (Mw / Mn): 10 to 14
[0051] (a5) In a temperature rising elution fractionation (TREF) analysis, based on the total weight of all eluted fractions,
[0052] Content of the polymer fraction eluted in the range of 25°C to 90°C: 20 wt% to 50 wt%, and
[0053] Content of the polymer fraction eluted in the range of 90°C to 120°C: 50 wt% to 80 wt%.
[0054] Specifically, in GPC analysis, the polyethylene resin composition shows a bimodal molecular weight distribution curve in a molecular weight distribution curve having a logarithmic value (logMw) of the weight average molecular weight (Mw, g / mol) on the x-axis and a molecular weight distribution relative to the log value (dwt / dlogMw) on the y-axis.
[0055] In the present disclosure, bimodal molecular weight distribution means that the molecular weight distribution curve has two peaks on the GPC graph. At this time, it also includes the case where the two peaks do not exist separately in the form of independent peaks, but partially overlap and exist as shoulder peaks and there is no minimum between the maximum values of the two peaks. In other words, the bimodal structure is defined as being deconvoluted into two distributions when it cannot be interpreted as a single peak forming a normal distribution.
[0056] This bimodal molecular weight distribution shows that the distribution of low molecular weight components and high molecular weight components in the polyethylene resin composition increases. Due to this molecular weight distribution structure, improved physical properties can be shown. Especially, compared with the polyethylene resin composition with unimodal molecular weight distribution, it can enhance the molecular structure that is conducive to biaxial stretching, thereby obtaining excellent stretchability.
[0057] Typically, biaxially oriented polyethylene (BOPE) films are produced by stretching a cast sheet in both the machine direction (MD) and the transverse direction (TD). Since biaxial stretching must be performed from MD stretching to TD stretching, the polyethylene used in the BOPE film requires excellent stretchability.
[0058] To ensure the stretchability of the polyethylene, secondary crystallization should occur as late as possible during longitudinal (MD) stretching. In addition, the polyethylene should have a structure that enables interlayer lateral bonding between sheets, thereby allowing subsequent stretching in the transverse direction (TD).
[0059] The polyethylene resin composition of the present disclosure has a controlled molecular structure achieved by optimally blending a first polyethylene (HDPE) having high density and controlled properties (eg, MI) with a second polyethylene (LDPE) having low density.
[0060] Specifically, in the polyethylene resin composition of the present disclosure, the first polyethylene can enhance rigidity by optimizing the ultrahigh molecular weight region, and the second polyethylene can strengthen the low molecular weight and low crystallinity regions to achieve interlayer chain movement, thereby improving the stretchability of the resin composition.
[0061] Furthermore, the polyethylene resin composition of the present disclosure exhibits a normal comonomer distribution and can exhibit excellent biaxial stretchability through β-relaxation.
[0062] β-Relaxation is caused by the movement of polymer chains between lamellar crystals, and this increase in fluidity can lead to excellent stretchability during film production.
[0063] Such β-relaxation can be confirmed by the presence of a peak (β-relaxation peak) which appears in the range of -40°C to 10°C in a temperature-dependent loss modulus graph obtained from dynamic mechanical analysis (DMA) of the polyethylene resin composition.
[0064] In addition, the polyethylene resin composition of the present disclosure has an optimized content distribution according to crystallinity. This optimized crystal distribution can be confirmed by TREF analysis.
[0065] Specifically, the polyethylene resin composition of the present disclosure meets the following TREF analysis conditions:
[0066] Content of the polymer fraction eluted in the range of 25°C to 90°C: 20 wt% to 50 wt%, based on the total weight of all eluted fractions, and
[0067] Content of the polymer fraction eluted in the range of 90°C to 120°C: 50 wt% to 80 wt%.
[0068] More specifically, in the TREF analysis, the content of the polymer fraction eluted in the range of 25°C to 90°C of the polyethylene resin composition is 20 wt% or more, 25 wt% or more, or 30 wt% or more, and 50 wt% or less, 45 wt% or less, 43 wt% or less, or 40 wt% or less, based on the total weight of all eluted fractions.
[0069] In addition, in the TREF analysis, the content of the polymer fraction eluted in the range of 90°C to 120°C of the polyethylene resin composition is 50 wt% or more, 55 wt% or more, 57 wt% or more, or 60 wt% or more, and 80 wt% or less, 75 wt% or less, or 70 wt% or less, based on the total weight of all eluted fractions.
[0070] Furthermore, the polyethylene resin composition may also meet the following TREF analysis conditions:
[0071] The content of the polymer fraction eluted in the range of 40° C. to 70° C. is 1 wt % to 30 wt % based on the total weight of all eluted fractions; and
[0072] Content of the polymer fraction eluted in the range of 100°C to 105°C: 30 wt% to 45 wt%.
[0073] More specifically, in the TREF analysis, the content of the polymer fraction eluted in the range of 45°C to 70°C of the polyethylene resin composition is 1 wt% or more, 2 wt% or more, 2.5 wt% or more, or 7 wt% or more, and 30 wt% or less, 25 wt% or less, 22 wt% or less, or 15 wt% or less, based on the total weight of all eluted fractions.
[0074] In addition, in the TREF analysis, the content of the polymer fraction eluted in the range of 100°C to 105°C of the polyethylene resin composition is 30 wt% or more, 33 wt% or more, or 35 wt% or more, and 45 wt% or less, 44.5 wt% or less, or 40 wt% or less, based on the total weight of all eluted fractions.
[0075] In the TREF analysis, a lower elution temperature means a lower crystallinity. The polymer fraction eluted in the range of 25°C to 90°C and the polymer fraction eluted in the range of 40°C to 70°C are both low crystalline fractions. When the above content conditions are met, the stretchability, toughness and transparency of the polyethylene resin composition can be improved.
[0076] Furthermore, the polymer fraction eluting in the range of 90°C to 120°C and the polymer fraction eluting in the range of 100°C to 105°C are both highly crystalline fractions, and when they satisfy the above-mentioned content conditions, the hardness of the polyethylene resin composition can be improved.
[0077] In particular, when a stretched film is manufactured, the polyethylene resin composition may exhibit excellent hardness and heat resistance because it has a high crystalline fraction content of 30 wt % or more.
[0078] Meanwhile, the content ratio of the fraction eluted in each elution temperature range of the polyethylene resin composition was calculated based on the total weight of all eluted fractions obtained by TREF analysis, and the content ratio of the polymer fraction eluted in the corresponding temperature range was calculated as percentage (wt %).
[0079] In addition, the detailed measurement method and conditions of the TREF analysis of the polyethylene resin composition are as described in the following Experimental Examples.
[0080] In addition to the above molecular structure, the melt index (MI) of the polyethylene resin composition of the present disclosure is measured at 190° C. under a load of 2.16 kg according to ASTM D1238. 2.16 ) can be 0.5 g / 10 min or more and 3.0 g / 10 min or less.
[0081] Generally, the lower the MI, the better the melt strength. Therefore, when producing an MDO film that prioritizes blow molding stability (or bubble stability), minimizing the thickness change or necking phenomenon reduces losses, thereby improving output and processability. However, if the MI is too low, excessive processing loads may be caused during the production of the MDO film, making film extrusion difficult. In addition, in the uniaxial stretching process, there is the following problem: the temperature needs to be increased to reduce the processing viscosity. On the other hand, a higher MI leads to better fluidity, making it advantageous for producing BOPE films using a casting process. In addition, when a biaxial stretching process is performed after manufacturing a cast sheet, a low molecular weight is required, so the MI must be high. However, if the MI is too high, the processing viscosity becomes too low, which reduces the process stability in the extrusion and stretching process. Therefore, the present invention controls the melt index of the polyethylene resin composition within the above range, ensuring excellent processability and being advantageous for both the extrusion and stretching processes.
[0082] More specifically, the melt index (MI 2.16 ) can be 0.5g / 10min or more, 0.8g / 10min or more, 0.85g / 10min or more, 0.87g / 10min or more, 0.94g / 10min or more, 1g / 10min or more, 1.2g / 10min or more, 1.21g / 10min or more, or 1.3g / 10min or more, and 3.0g / 10min or less, 2.5g / 10min or less, 2.0g / 10min or less, 1.5g / 10min or less, 1.49g / 10min or less, or 1.45g / 10min or less.
[0083] In addition, the polyethylene resin composition of the present disclosure has a viscosity of 0.940 g / cm 3 Up to 0.955g / cm 3 Therefore, it can show excellent strength. More specifically, the density of the polyethylene resin composition can be 0.940 g / cm 3 Above, 0.942g / cm 3 Above, or 0.944g / cm 3 Above, and 0.955g / cm 3 Below, 0.954g / cm 3 Below, 0.951g / cm 3 Below, 0.950g / cm 3 Below, or 0.949g / cm 3 the following.
[0084] Meanwhile, the density of the polyethylene resin composition was measured according to ASTM D792 standard.
[0085] In addition, the MFRR (MI 21.6 / MI 2.16 ) is greater than 60 and less than 80, where MFRR(MI 21.6 / MI 2.16 ) is measured as follows: The melt index (MI) measured according to ASTM D1238 at 190°C and a load of 21.6 kg 21.6 ) divided by the melt index (MI) measured at 190°C and 2.16 kg load according to ASTM D1238 2.16 ). More specifically, MFRR(MI 21.6 / MI 2.16 ) can be greater than 60, greater than 60.5, greater than 61, or greater than 63, and less than 80, less than 77, less than 75, or less than 70.
[0086] In addition, the molecular weight distribution (Mw / Mn) of the polyethylene resin composition is 10 or more and 14 or less. More specifically, the molecular weight distribution may be 10 or more, 10.5 or more, 10.8 or more, or 11 or more, and 14 or less, 13.8 or less, 13 or less, or 12 or less.
[0087] In the present disclosure, the molecular weight distribution of the polyethylene resin composition can be obtained by measuring the weight average molecular weight (Mw) and the number average molecular weight (Mn) by gel permeation chromatography (GPC) analysis, and dividing the weight average molecular weight (Mw) by the number average molecular weight (Mn). Wherein, the weight average molecular weight and the number average molecular weight are values converted to standard polystyrene. The detailed measurement method and conditions are described in the following experimental examples.
[0088] In addition, in addition to the above physical property requirements, the polyethylene resin composition of the present disclosure may also meet one or more, two or more, or all three of the following conditions (b1) to (b3):
[0089] (b1) Weight average molecular weight (Mw): 100,000 g / mol to 160,000 g / mol
[0090] (b2) Relaxation time: 0.1 to 0.9 seconds
[0091] (b3) Shear thinning index: 0.2 to 0.5
[0092] Specifically, the polyethylene resin composition of the present disclosure may have a weight average molecular weight (Mw) of 100,000 g / mol or more and 160,000 g / mol or less.
[0093] Too high Mw is disadvantageous for casting and BOPE manufacturing processes, and too low Mw is disadvantageous for blow molding and MDO manufacturing processes due to low melt strength. In the present disclosure, casting and BOPE manufacturing processes and blow molding and MDO manufacturing processes can be performed by controlling Mw within the above range.
[0094] More specifically, the weight average molecular weight (Mw) of the polyethylene resin composition may be 100,000 g / mol or more, 110,000 g / mol or more, or 120,000 g / mol or more, and 160,000 g / mol or less, 155,000 g / mol or less, 150,000 g / mol or less, 148,000 g / mol or less, 147,000 g / mol or less, or 146,800 g / mol or less.
[0095] Meanwhile, in the present disclosure, the weight average molecular weight (Mw) and number average molecular weight (Mn) of the polyethylene resin composition can be determined by gel permeation chromatography (GPC) analysis, and each is a value converted to standard polystyrene. The detailed measurement method and conditions are described in the following experimental examples.
[0096] Furthermore, the polyethylene resin composition exhibits a long relaxation time of 0.1 to 0.9 seconds.
[0097] The bimodal high-density polyethylene used to make conventional stretch films has a short relaxation time and a high crystallinity, resulting in poor stretchability. Specifically, the short relaxation time results in rapid stress relaxation, which increases dislocation and shrinkage, thereby resulting in uneven layers, uneven film thickness distribution, and film breakage. However, even under equal melt index conditions, the polyethylene resin composition of the present disclosure can also exhibit a longer relaxation time, and therefore, can exhibit excellent stretchability by mixing a second polyethylene with a long relaxation time and a low crystallinity during manufacture.
[0098] Meanwhile, the relaxation time of the polyethylene resin composition can be determined by continuously applying strain (0.5%) within the linear viscosity range at a temperature of 190° C. and an angular frequency of 0.01 Hz to 100 Hz (0.0628 rad / s to 628 rad / s) using a rotational rheometer, and conducting an oscillatory shear test to measure the viscosity of the polyethylene resin composition, followed by calculation using the Carreau-Yasuda model of Formula 1 below.
[0099] [Formula 1]
[0100]
[0101] In equation 1,
[0102] η is the viscosity of the polyethylene resin composition measured above (Pa·s), and
[0103] η0 is zero shear viscosity (Pa·s), which is the viscosity in a region where the viscosity does not change when the angular frequency approaches zero. In the present disclosure, the zero shear viscosity can be determined by fitting a log-log plot of the angular frequency (unit: Hz) on the x-axis and the viscosity η (unit: Pa·s) of the polyethylene resin composition measured as above on the y-axis to the Carreau-Yasuda model represented by Formula 1.
[0104] in addition, represents the shear rate applied to the polyethylene resin composition, which is the same as the angular frequency converted into rad / s according to the Cox-Merz rule.
[0105] λ is the relaxation time (seconds) of the polyethylene resin composition and can be determined by fitting a log-log plot of angular frequency (Hz) on the x-axis and viscosity η (Pa·s) of the polyethylene resin composition measured as above on the y-axis to the Carreau-Yasuda model represented by Formula 1.
[0106] In addition, n is a shear thinning index and can be determined by fitting a log-log plot of angular frequency (Hz) on the x-axis and viscosity η (Pa·s) of the polyethylene resin composition measured above on the y-axis to the Carreau-Yasuda model represented by Formula 1.
[0107] a is a shape parameter for transition from a Newtonian plateau to a power law region, and can be determined by fitting a log-log plot of angular frequency (Hz) on the x-axis and viscosity η (Pa·s) of the polyethylene resin composition measured as above on the y-axis to a Carreau-Yasuda model represented by Formula 1.
[0108] More specifically, the polyethylene resin composition may have a long relaxation time of 0.1 second or more, 0.15 second or more, 0.17 second or more, or 0.2 second or more, and 0.9 second or less, 0.89 second or less, 0.7 second or less, 0.68 second or less, or 0.65 second or less.
[0109] The method of measuring the relaxation time of the polyethylene resin composition will be described in detail below in Examples.
[0110] In addition, the polyethylene resin composition has a shear thinning index of 0.2 to 0.5.
[0111] The shear thinning index represents the crystallization rate and the uniformity of the crystallization rate. The higher the shear thinning index, the slower the crystallization rate, and the higher the uniformity of the crystallization rate, indicating excellent stretchability. The polyethylene used to make conventional stretch films has a high degree of crystallinity and therefore exhibits a low shear thinning index. Therefore, a fast crystallization rate and low uniformity of the crystallization rate can lead to unstable crystallization behavior and deterioration of stretchability. On the other hand, the polyethylene resin composition of the present invention exhibits a high shear thinning index by using a mixture of a second polyethylene with a long relaxation time and low crystallinity during the production process. Therefore, the crystallization rate is slow and the uniformity of the crystallization rate is high, showing stable crystallization behavior and excellent stretchability. In addition, as the shear thinning index is within the above range, it can exhibit better stretchability.
[0112] More specifically, the polyethylene resin composition may exhibit a shear thinning index of 0.2 or more, 0.22 or more, or 0.25 or more, and 0.5 or less, 0.4 or less, or 0.36 or less.
[0113] In the present disclosure, the shear thinning index of the polyethylene resin composition can be determined by continuously applying strain (0.5%) within the linear viscosity range using a rotational rheometer at a temperature of 190° C. and an angular frequency of 0.01 Hz to 100 Hz (0.0628 rad / s to 628 rad / s), and performing an oscillatory shear experiment to measure the viscosity of the polyethylene resin composition, and then fitting a log-log plot with the angular frequency (Hz) on the x-axis and the viscosity η (Pa·s) of the polyethylene resin composition measured on the y-axis to the Carreau-Yasuda model represented by Formula 1.
[0114] The polyethylene resin composition of the present disclosure satisfies all of the above-mentioned molecular structure and physical property conditions, and thus can exhibit excellent stretchability, high mechanical properties and transparency. As a result, when a biaxially stretched film is manufactured, there is no risk of defects such as breakage or shrinkage in the TD direction stretching process, and the resulting biaxially stretched film can exhibit excellent stretchability, high mechanical strength and transparency.
[0115] Meanwhile, the polyethylene resin composition of the present disclosure comprises a density (ASTM D792) of 0.950 g / cm 3 Above and MI 2.16 A first polyethylene having an OD of 0.5 g / 10 min to 2 g / 10 min (ASTM D1238, 190° C., 2.16 kg), and a density of 0.925 g / cm 3 The following and MI 2.16 The second polyethylene having a molecular weight of 1 g / 10 min to 5 g / 10 min (ASTM D1238, 190° C., 2.16 kg).
[0116] The first polyethylene is produced by a multimodal slurry polymerization process using multiple reactors and a Ziegler-Natta catalyst, which is advantageous for a wide molecular weight distribution, thereby satisfying all of the above physical property conditions and further satisfying the following conditions (c1) to (c5). Therefore, the first polyethylene can improve hardness and stiffness by increasing the content of the ultrahigh molecular weight region in the polyethylene resin composition:
[0117] (c1) Density (ASTM D792): 0.950 g / cm 3 Above, or 0.952g / cm 3 Above, and 0.965g / cm 3 Below, 0.960g / cm 3 Below, or 0.958g / cm 3 the following,
[0118] (c2)MI 2.16 (ASTM D1238, 190°C, 2.16kg): 0.5 g / 10 min or more, 0.8 g / 10 min or more, or 1 g / 10 min or more, and 2 g / 10 min or less, or 1.5 g / 10 min or less,
[0119] (c3)MFRR(MI 21.6 / MI 2.16 ): 50 or more, or 80 or more, and 100 or less, 90 or less, or 85 or less.
[0120] (c4) weight average molecular weight (Mw): 130,000 g / mol or more, 140,000 g / mol or more, or 142,000 g / mol or more, and 160,000 g / mol or less, 155,000 g / mol or less, or 150,000 g / mol or less,
[0121] (c5) Molecular weight distribution (Mw / Mn): 10 or more, 13 or more, 14 or more, or 14.1 or more, and 16 or less, 15.5 or less, or 15.2 or less.
[0122] The first polyethylene may specifically be one or more of an ethylene homopolymer and an ethylene / C4-C8 alpha olefin copolymer. In addition, the ethylene / C4-C8 alpha olefin copolymer may be an ethylene / 1-butene copolymer.
[0123] At the same time, the second polyethylene is produced by a unimodal slurry polymerization process using a single reactor and a metallocene catalyst, thereby satisfying the following conditions (d1) to (d5). Therefore, the second polyethylene can enhance the low molecular weight crystallinity and enhance the tensile processability by interlayer chain migration in the polyethylene resin composition:
[0124] (d1) Density (ASTM D792): 0.910 g / cm 3 Above, and 0.925g / cm 3 Below, 0.920g / cm 3 Below, or 0.918g / cm 3 the following,
[0125] (d2)MI 2.16 (ASTM D1238, 190°C, 2.16kg): 1g / 10min or more and 5g / 10min or less, or 3g / 10min or less,
[0126] (d3)MFRR(MI 21.6 / MI 2.16 ): 10 or more, or 15 or more, and 50 or less, or 20 or less,
[0127] (d4) weight average molecular weight (Mw): 50,000 g / mol or more, or 70,000 g / mol or more, and 130,000 g / mol or less, or 120,000 g / mol or less,
[0128] (d5) Molecular weight distribution (Mw / Mn): 1 or more, 2 or more, or 2.4 or more, and 10 or less, 3 or less, or 2.5 or less.
[0129] At the same time, the polyethylene resin composition exhibits excellent stretchability because it shows a long relaxation time and a slow crystallization rate. In the case of the first polyethylene, the disadvantages are that the relaxation time is short due to the high density and the stretchability is poor due to the high crystallinity. In contrast, the second polyethylene has a long relaxation time and a high shear thinning index and exhibits a T in the loss modulus (E") curve. β peak, thereby compensating for the shortcomings of the first polyethylene.
[0130] The second polyethylene may be one or more of ethylene / C4-C8 alpha olefin copolymers, and more specifically, may be ethylene / 1-hexene copolymer or ethylene / 1-octene copolymer.
[0131] The weight ratio of the first polyethylene and the second polyethylene included is 90:10-70:30. When the above weight ratio condition is met, the physical properties of the above polyethylene resin composition are easily achieved, and the improvement effect is also excellent. More specifically, the first polyethylene and the second polyethylene can be mixed in a weight ratio of 90:10 to 77:23, 90:10 to 80:20, 90:10 to 83:17, 83:17 to 70:30, 80:20 to 70:30, or 77:23 to 70:30.
[0132] Meanwhile, the polyethylene resin composition of the present disclosure can be prepared by a preparation method comprising the following steps: a first step, carrying out a primary polymerization reaction of ethylene monomer in a first reactor in the presence of a Ziegler-Natta catalyst, transferring the obtained polymerization product to a second reactor, and adding one or more ethylene monomers and C4-C8 alpha olefin monomers to carry out a secondary polymerization reaction to prepare a first polyethylene;
[0133] The second step is to produce a second polyethylene by polymerizing an ethylene monomer and a C4-C8 α-olefin monomer in the presence of a catalyst in a separate single reactor while introducing hydrogen, wherein the catalyst comprises a metallocene compound represented by the following Chemical Formula 1; and
[0134] The third step is to mix the first polyethylene and the second polyethylene in a weight ratio of 90:10 to 70:30;
[0135] [Chemical formula 1]
[0136]
[0137] In Chemical Formula 1,
[0138] B is boron,
[0139] M is a Group 4 transition metal,
[0140] R1 to R4 are each independently hydrogen, C 1-20 Alkyl, C 3-20 Cycloalkyl or C 6-20 Aryl, or R1 and R2, or R3 and R4 are connected to each other to form a substituted or unsubstituted C 6-60 Aromatic rings,
[0141] R5 and R6 are each independently C 1-20 Alkyl, C 3-20 Cycloalkyl or C 6-20 Aryl, or R5 and R6 are connected to each other to form a C 3-60 Alicyclic or C 6-60 Aromatic rings,
[0142] X1 and X2 are each independently C 1-20 Alkyl or -O(CO)R', where R' is C 1-20 alkyl,
[0143] Q is substituted or unsubstituted C 2-60 a heterocyclic ring comprising at least one selected from the group consisting of N, O and S,
[0144] Y and Y' are the elements that make up Q,
[0145] Y is N, O or S, and
[0146] Y' is an element of Q adjacent to Y and is N or C.
[0147] Unless otherwise specified herein, the following terms may be defined as follows.
[0148] The halogen may be fluorine (F), chlorine (Cl), bromine (Br) or iodine (I).
[0149] The alkyl group may be a straight chain or a branched chain. 1-20 The alkyl group can be C 1-20 Straight chain alkyl, C 1-10 Straight chain alkyl, C 1-5 Straight chain alkyl, C 3-20 Branched alkyl, C 3-15 Branched alkyl, or C 3-10 More specifically, C 1-20 The alkyl group may be methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl or isopentyl, but the present disclosure is not limited thereto. Meanwhile, as used herein, "iPr" refers to an isopropyl group.
[0150] The cycloalkyl group may be a cyclic alkyl group. 3-20 The cycloalkyl group may be C 3-20 Cyclic alkyl, C 3-15 Cyclic alkyl, or C 3-10 Cyclic alkyl. More specifically, it can be cyclopropyl, cyclobutyl, cyclopentyl, 3-methylcyclopentyl, 2,3-dimethylcyclopentyl, cyclohexyl, 3-methylcyclohexyl, 4-methylcyclohexyl, 2,3-dimethylcyclohexyl, 3,4,5-trimethylcyclohexyl, 4-tert-butylcyclohexyl, cycloheptyl, cyclooctyl, etc., but the present disclosure is not limited thereto. Meanwhile, as used herein, "Cy" refers to a C3 to C6 cycloalkyl.
[0151] The alkenyl group may be a straight chain, branched chain or cyclic alkenyl group. 2-20 The alkenyl group may be C 2-20 Straight chain alkenyl, C 2-10 Straight chain alkenyl, C 2-5 Straight chain alkenyl, C 3-20 Branched alkenyl, C 3-15 Branched alkenyl, C 3-10 Branched alkenyl, C 5-20 Cycloalkenyl or C 5-10 More specifically, C 2-20 The alkenyl group may be ethenyl, propenyl, butenyl, pentenyl, cyclohexenyl, or the like.
[0152] The alkoxy group may be a linear, branched or cyclic alkoxy group. 1-20 The alkoxy group may be C 1-20 Straight chain alkoxy, C1-10 Straight chain alkoxy, C 1-5 Straight chain alkoxy, C 3-20 Branched or cyclic alkoxy, C 3-15 Branched or cyclic alkoxy, or C 3-10 More specifically, C 1-20 The alkoxy group may be a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an n-butoxy group, an isobutoxy group, a tert-butoxy group, an n-pentyloxy group, an isopentyloxy group, a neopentyloxy group, or a cyclohexyloxy group, but the present disclosure is not limited thereto.
[0153] The alkoxyalkyl group may have a a -OR b The structure may be one in which the alkyl group (-R a ) is replaced by an alkoxy group (-OR b ) substituted substituent. Specifically, C 2-20 The alkoxyalkyl group may be methoxymethyl, methoxyethyl, ethoxymethyl, isopropoxymethyl, isopropoxyethyl, isopropoxyhexyl, tert-butoxymethyl, tert-butoxyethyl, tert-butoxyhexyl or the like.
[0154] The aryl group may be a monocyclic, bicyclic or tricyclic aromatic hydrocarbon. According to an embodiment of the present disclosure, the aryl group may have 6 to 60 carbon atoms, or 6 to 20 carbon atoms. Specifically, the aryl group may be a phenyl group, a naphthyl group, an anthracenyl group, a dimethylanilino group, an methoxyphenyl group, etc., but is not limited thereto.
[0155] The heteroaryl group is a heteroaryl group containing at least one of O, N, and S as a heteroelement, and may have 2 to 60 carbon atoms, or 2 to 20 carbon atoms, although the number of carbon atoms is not particularly limited. Specifically, it can be xanthene, thioxanthene, thienyl, furanyl, pyrrolyl, imidazolyl, thiazolyl, oxazolyl, oxadiazolyl, triazolyl, pyridyl(), bipyridyl, pyridyl, pyrimidinyl, triazine, acridinyl, pyridazinyl, pyrazinyl, quinolyl, quinazolinyl, quinoxalinyl, phthalazinyl, pyridopyrimidinyl, pyridopyrazinyl, pyrazinopyrazinyl, isoquinolyl, indolyl, carbazolyl, benzoxazolyl, benzimidazolyl, benzothiazolyl, benzocarbazolyl, benzothienyl, dibenzothienyl, benzofuranyl, phenanthrolinyl, isoxazolyl, thiadiazolyl, phenothiazinyl, dibenzofuranyl, etc., but the present disclosure is not limited thereto.
[0156] In addition, the heterocyclic ring includes an alicyclic ring containing at least one selected from the group consisting of N, O and S and an aromatic ring containing at least one selected from the group consisting of N, O and S.
[0157] In addition, the fourth group transition metal may be titanium (Ti), zirconium (Zr), hafnium (Hf) or rubidium (Rf), and specifically titanium (Ti), zirconium (Zr) or hafnium (Hf). More specifically, it may be zirconium (Zr) or hafnium (Hf), but is not limited thereto.
[0158] The above-mentioned substituents may be optionally substituted by one or more selected from the group consisting of the following substituents, within the scope of exhibiting the same or similar effects as the desired effects: hydroxyl; halogen; alkyl or alkenyl, aryl, alkoxy; alkyl or alkenyl, aryl, alkoxy containing at least one heteroatom of Group 14 to Group 16 heteroatom; amino; silyl; alkylsilyl or alkoxysilyl; phosphino; phosphide group; sulfonate group; and sulfone group.
[0159] Hereinafter, each step is described in detail.
[0160] First, the first step of preparing the polyethylene resin composition of the present disclosure is a first polyethylene production step.
[0161] Specifically, the first polyethylene can be produced by performing a primary polymerization of ethylene monomer in the presence of a Ziegler-Natta catalyst in a first reactor, transferring the resulting polymerization product to a second reactor, and adding at least one of ethylene monomer and C4-C8 α-olefin monomer to perform a secondary polymerization reaction.
[0162] When a plurality of reactors are used to produce the first polyethylene by slurry polymerization, two or more reactors may be used, for example, two or more continuous stirred tank reactors (CSTRs). Specifically, in the above-mentioned preparation method, a first reactor and a second reactor may be used, in which a primary slurry polymerization reaction for producing the first polyethylene occurs, and the second reactor is connected to the first reactor, in which a secondary slurry polymerization reaction occurs.
[0163] In addition, the polymerization method in the first reactor and the second reactor is performed using a slurry polymerization method.
[0164] In the case of solution polymerization, the catalyst is activated by high temperature and high pressure reaction, so that the prepared resin composition exhibits deteriorated stretchability due to narrow molecular weight distribution (MWD) and low high molecular weight tail content. However, since the slurry polymerization method in the present disclosure is carried out at a relatively low temperature, a molecular structure with a wide MWD and a high high molecular weight tail content, which is required for a polyethylene resin composition for producing a transparent film, can be ensured. As a result, excellent biaxial stretchability can be achieved.
[0165] The Ziegler-Natta catalyst used to prepare the first polyethylene may specifically be a magnesium-supported titanium catalyst. Further, the magnesium-supported titanium catalyst may further contain a halogenated hydrocarbon.
[0166] Specifically, the magnesium-supported titanium catalyst includes a solid magnesium carrier. Examples of magnesium carriers may include magnesium, magnesium oxide, magnesium chloride, silicon dioxide-magnesium oxide, magnesium oxide, etc., and any one thereof, or a mixture of two or more thereof may be used. Among them, the magnesium carrier may be magnesium, considering the catalytic activity and the ease of achieving the best physical properties of the polyethylene resin composition.
[0167] Meanwhile, the magnesium-supported titanium catalyst includes a titanium-containing compound shown in the following Chemical Formula 2 as a main catalyst:
[0168] [Chemical formula 2]
[0169] Ti(OR 1 ) m X 1 4-m
[0170] In chemical formula 2,
[0171] R 1 are the same or different and are alkyl groups having 1 to 10 carbon atoms,
[0172] X 1 is a halogen atom, more specifically, Cl, Br or I, and
[0173] M is an integer from 0 to 4.
[0174] In chemical formula 2, R 1 Specifically, it may be an alkyl group having 1 or more, 2 or more, or 3 or more, and 10 or less, 8 or less, or 5 or less carbon atoms.
[0175] Furthermore, X 1 Specifically, it may be Br or Cl, and more specifically, it may be Cl.
[0176] Specific examples of the titanium-containing compound may include titanium tetrachloride (TiCl 4 ) or titanium oxychloride, and either one or a mixture of both may be used.
[0177] In addition, the catalyst containing the titanium-containing compound may include Mg:Ti in a molar ratio of 1:1 to 10:1, 2:1 to 7:1, or 4:1 to 5:1, based on the content of Mg in the magnesium support and the content of Ti in the titanium-containing compound. When included within the above molar ratio range, excellent catalytic activity can be achieved.
[0178] Furthermore, the shape of the catalyst is not particularly limited, but it may be in the form of, for example, spherical fine particles.
[0179] In addition, the average particle size of the catalyst may be 5 μm to 100 μm, more specifically, 5 μm or more, 8 μm or more, or 10 μm or more, and 100 μm or less, 50 μm or less, 20 μm or less, or 13 μm or less.
[0180] Meanwhile, the average particle size of the catalyst in the present disclosure can be measured by scanning electron microscopy (SEM) observation. Specifically, after obtaining an SEM image in which more than 100 catalyst particles are observed, a random straight line is drawn, and the average size of the catalyst particles can be calculated based on the length of the corresponding straight line, the number of particles contained in the straight line, and the magnification.
[0181] Furthermore, the magnesium-supported titanium catalyst may further contain halogenated hydrocarbons.
[0182] The halogenated hydrocarbons change the electrical properties of titanium by coordinating around titanium as active sites, and a large amount of halogenated hydrocarbons create sufficient three-dimensional space between titanium atoms, thereby greatly improving the catalytic activity in the polyethylene polymerization process.
[0183] The halogenated hydrocarbon may be specifically an alkane having 1 to 12 carbon atoms, a cycloalkane having 3 to 12 carbon atoms, an alkene having 2 to 12 carbon atoms, an alkyne having 2 to 12 carbon atoms, or an aromatic hydrocarbon having 6 to 30 carbon atoms substituted with one or more halogen groups. The halogen group may be fluorine, chlorine or bromine.
[0184] Specific examples may include bromoform, tetrachloroethane, hexachloroethane, pentachloroethane, 1,1,2,2-tetrachloroethane, 1-bromo-1-chloroethane, 1,2-dibromoethane, 1,2-dichloroethane, bromoethane, hexachloropropane, 1,2,3-trichloropropane, 1,2-dichloropropane, 1-chloropropane, 2-chloropropane, chlorobutane, dichlorobutane, 1-chloro-2-methylpropane, n-butyl chloride, tert-butyl chloride, 1-chloro-3-methylbutane, 1-chloropentane, 1,5- Dichloropentane, bromopentane, neopentyl chloride, 1-chloroheptane, cyclopropyl bromide, cyclobutyl chloride, chlorocyclohexane, cyclohexyl bromide, vinylidene chloride, 1,2,3,3-tetrachloropropene, 1,2-dibromo-1-propene, 1,3-dichloropropene, hexachloro-1,3-butadiene, 2-bromo-2-butene, propargyl chloride, chlorobenzene, tetrachlorobenzene, trichlorobenzene, dichlorobenzene, 4-chlorobenzyl chloride, benzyl chloride, or 1,1-dichloro-2-phenylcyclopropane, and mixtures of two or more thereof.
[0185] Based on 1 mol of the titanium-containing compound as the main catalyst, the content of the halogenated hydrocarbon can be more than 0.1 mol, more than 0.12 mol, or more than 0.13 mol, and less than 500 mol, less than 100 mol, less than 50 mol, less than 10 mol, less than 1 mol, or less than 0.5 mol.
[0186] The Ziegler-Natta catalyst can be prepared by the following preparation method, which includes: a carrier treatment step, mixing and reacting the raw material of the magnesium carrier with an alcohol; and a titanium-containing compound loading step, reacting the product produced by the above step with the titanium-containing compound represented by Chemical Formula 1; and further including a step of contacting and reacting with a halogenated hydrocarbon during the carrier treatment step and the titanium-containing compound loading step or after the titanium-containing compound loading step. Therefore, the method for preparing a polyethylene resin composition disclosed in the present invention includes a specific carrier treatment step and a titanium-containing compound loading step before the first step, that is, the step of preparing the Ziegler-Natta catalyst, and may also include a step of contacting and reacting with a halogenated hydrocarbon during the carrier treatment step and the titanium-containing compound loading step or after the titanium-containing compound loading step.
[0187] Specifically, the support treatment step for preparing the Ziegler-Natta catalyst may be performed by mixing and reacting a raw material of the magnesium support with an alcohol in a non-polar solvent.
[0188] Specific examples of alcohols may include methanol, ethanol, 1-propanol, isopropanol, n-butanol, isobutanol, 1-pentanol, isopentanol, n-hexanol, 1-octanol, 2-ethyl-1-hexanol, etc., and any one thereof or a mixture of two or more thereof may be used. Among them, ethanol or 2-ethyl-1-hexanol may be used.
[0189] The amount of the alcohol used may be 1 mol or more, 1.5 mol or more, or 2 mol or more, and 10 mol or less, 8 mol or less, or 6 mol or less, based on 1 mol of the raw material of the magnesium support.
[0190] Meanwhile, the raw material of the magnesium carrier may include the magnesium carrier itself, such as magnesium, magnesium oxide, magnesium chloride or silicon dioxide-magnesium oxide, etc.; or a magnesium alcohol compound, such as magnesium ethoxide, etc., and any one thereof, or a mixture of two or more thereof may be used. For example, when a magnesium alcohol compound is used as the raw material of the magnesium carrier, it is converted into magnesium chloride by titanium tetrachloride (TiCl4) introduced as a main catalyst, so as to be included as a carrier in the final catalyst.
[0191] The method of mixing the raw material of the magnesium support with alcohol can be specifically performed as follows: the alcohol is added to a slurry prepared by mixing the raw material of the magnesium support with a non-polar solvent such as hexane, or a solution in which the alcohol is dissolved in the non-polar solvent is added to the slurry, and then the solution is stirred at a temperature of 20° C. to 150° C. until it becomes a transparent solution. As a result of the above mixing, a uniform solution of the magnesium support is obtained, and in the solution, an adduct is formed in which crystals of the magnesium support are surrounded by alcohol molecules.
[0192] Next, the reaction product of the magnesium support and the alcohol generated in the support treatment step is reacted with a titanium-containing compound, thereby performing a step of supporting the titanium-containing compound for preparing a Ziegler-Natta catalyst.
[0193] Specifically, a titanium compound or a solution of a titanium compound dissolved in a non-polar solvent is directly added to the reaction product of the magnesium support and alcohol generated in the support treatment step, and reacted at -50°C to 120°C or -20°C to 80°C.
[0194] The type and content of the titanium-containing compound are as described above.
[0195] Furthermore, when the titanium-containing compound is introduced, the reaction product of the magnesium support and the alcohol generated in the support treatment step may be stirred at 10 rpm to 500 rpm or 50 rpm to 400 rpm.
[0196] Meanwhile, when preparing the Ziegler-Natta catalyst, the halogenated hydrocarbon is introduced when the alcohol is added to the magnesium support in the support treatment step; the halogenated hydrocarbon is introduced when the titanium-containing compound is introduced in the titanium-containing compound loading step; or after completing the step of loading the titanium-containing compound, a step of adding the halogenated hydrocarbon and reacting can be further performed.
[0197] The type and content of the halogenated hydrocarbon are as described above.
[0198] The Ziegler-Natta catalyst prepared by the above preparation method can be used directly in the polyethylene polymerization process, and can also be used as a slurry in a non-polar solvent.
[0199] In addition, the Ziegler-Natta catalyst may be used together with an organic metal compound represented by the following Chemical Formula 3 serving as a co-catalyst.
[0200] [Chemical formula 3]
[0201] R 2 n MX 2 (3-n)
[0202] In chemical formula 3,
[0203] M is selected from the group consisting of elements of Groups IB, IIA, IIIB and IVB of the Periodic Table,
[0204] R 2 are the same or different and are alkyl groups having 1 to 10 carbon atoms,
[0205] X 2 is a halogen, and
[0206] n is an integer of 1 to 3.
[0207] In Chemical Formula 3, M is specifically aluminum, and R 2 is an alkyl group having 1 to 5 carbon atoms or 2 to 4 carbon atoms, and X 2 It is Cl or Br.
[0208] Specific examples of the organic metal compound represented by Chemical Formula 3 may include triethylaluminum, methylaluminum dichloride, methylaluminum dibromide, dimethylaluminum chloride, dimethylaluminum bromide, propylaluminum dichloride, propylaluminum dibromide, butylaluminum dichloride, butylaluminum dibromide, dibutylaluminum chloride, dibutylaluminum bromide, isobutylaluminum dichloride, isobutylaluminum dibromide, diisobutylaluminum chloride, diisobutylaluminum bromide, hexylaluminum dichloride, hexylaluminum dibromide, dihexylaluminum chloride, dihexylaluminum bromide, octylaluminum dichloride, octylaluminum dibromide, dioctylaluminum chloride, and dioctylaluminum bromide, and any one of them or a mixture of two or more thereof may be used.
[0209] At the same time, since the co-catalyst affects the polymerization activity of the magnesium-supported catalyst, the polymerization activity of the catalyst can be further increased by controlling the content of the co-catalyst. For example, for the organic metal compound represented by Chemical Formula 3, aluminum can be used in an amount of 3 mol or more, 10 mol or more, or 25 mol or more, and 200 mol or less, or 100 mol or less per 1 mol of titanium in the catalyst.
[0210] The cocatalyst can be added to the polyethylene polymerization reaction after being mixed with the Ziegler-Natta catalyst, or can be added separately before or after the Ziegler-Natta catalyst is added. Therefore, when preparing the first polyethylene in the first step according to the method for preparing a polyethylene resin composition of the present disclosure, a step of adding a cocatalyst can also be included.
[0211] Furthermore, a primary polymerization reaction was carried out while introducing hydrogen.
[0212] Because the input amount of hydrogen affects the physical properties of the prepared copolymer, the input amount is appropriately determined according to the physical properties to be achieved. For example, in the present disclosure, based on the gross weight of the ethylene monomer introduced into the first reactor, the total input amount of the hydrogen introduced in the primary polymerization reaction can be 0.001wt% to 0.5wt%. When hydrogen is introduced within the above range, the combined physical properties of the above-mentioned polyethylene resin composition can be easily achieved. More specifically, the amount of hydrogen introduced can be more than 0.001wt%, more than 0.01wt%, more than 0.05wt% or more than 0.07wt%, and less than 0.5wt%, less than 0.3wt% or less than 0.15wt%.
[0213] The reaction product obtained after the polymerization reaction under the above polymerization conditions is continuously transferred to the second reactor connected to the first reactor.
[0214] In the second reactor, an additional polymerization reaction occurs between the first polyethylene transferred from the first reactor and the ethylene or C4 to C10 alpha olefin second comonomer introduced into the second reactor.
[0215] The secondary polymerization reaction may be carried out in the presence of a catalyst.
[0216] In this case, as described in the first step, the catalyst suitable is a Ziegler-Natta catalyst. Therefore, the Ziegler-Natta catalysts used for the primary and secondary slurry polymerization reactions may be the same or different from each other. When the same Ziegler-Natta catalyst is used in the primary and secondary polymerization reactions, the physical properties of the polyethylene resin composition to be prepared can be more easily controlled, and thus the above-mentioned physical property requirements can be achieved.
[0217] Further, the secondary polymerization reaction can be carried out with or without the addition of hydrogen. For example, when hydrogen is introduced, the amount of hydrogen introduced can be 0.001 wt% to 0.05 wt% based on the total weight of the monomers including ethylene and the second alpha olefin comonomer introduced into the second reactor.
[0218] Furthermore, during the secondary polymerization reaction, only ethylene may be added without adding a comonomer, or a C4-C8 α-olefin may be added as a comonomer.
[0219] When C4-C8 alpha olefin is added as a comonomer during the secondary polymerization reaction, the total amount of ethylene added to the first and second reactors and the total amount of the comonomer may satisfy a weight ratio of 1:0.001 to 1:0.1. When the total amount of ethylene added to the first and second reactors and the total amount of the comonomer satisfy the above weight ratio range, the physical properties of the above polyethylene resin composition may be more easily achieved.
[0220] In addition, the polymerization temperature (T1) and pressure (P1) during the primary polymerization reaction are higher than the polymerization temperature (T2) and pressure (P2) during the secondary polymerization reaction. By controlling the amount of comonomer introduced during the primary polymerization reaction and setting higher temperature and pressure, it is easier to achieve a bimodal molecular weight distribution and an NCD structure in the polyethylene resin composition.
[0221] Specifically, the difference (T1-T2) between the polymerization temperature (T1) during the primary polymerization reaction and the polymerization temperature (T2) during the secondary polymerization reaction may be 3°C or more, 4°C or more, or 5°C or more, and 10°C or less, 8°C or less, or 6°C or less.
[0222] In addition, the difference (P1-P2) between the pressure during the primary polymerization reaction (P1) and the pressure during the secondary polymerization reaction (P2) may be 2 bar or more, 3 bar or more, or 3.2 bar or more, and 6 bar or less, 5.5 bar or less, or 5.3 bar or less.
[0223] In addition, in the preparation method disclosed herein, while satisfying the above-mentioned temperature difference and pressure difference, the polymerization temperature (T1) in the primary polymerization reaction process can be 70°C-90°C, and the polymerization temperature (T2) in the secondary polymerization reaction process can be 70°C-90°C.
[0224] In addition, the pressure during the primary polymerization reaction (P1) may be 5 bar to 10 bar, and the pressure during the secondary polymerization reaction (P2) may be 1 bar to 5 bar.
[0225] Through the above two-step polymerization method, the first polyethylene satisfying the above physical properties is obtained.
[0226] Subsequently, the second step is a production step of the second polyethylene.
[0227] The second polyethylene may be prepared by polymerizing an ethylene monomer and a C4-C8 alpha olefin monomer in the presence of a catalyst containing a metallocene compound represented by Chemical Formula 1 in a separate single reactor while introducing hydrogen.
[0228] Unlike conventionally used CGC (constrained geometry catalyst) type precursors, the metallocene compound represented by Chemical Formula 1 adopts a bridge structure containing a boron anion. Conventional CGC type precursors have a neutral bridge structure containing silicon, so that the ligand unit is negatively charged. This leads to structural limitations, and there is a problem that it is difficult to achieve various physical properties when preparing olefin polymers.
[0229] On the other hand, because the bridge structure is negatively charged, the metallocene compound represented by Chemical Formula 1 of the present disclosure may have a neutral ligand unit. The ligand unit of the present disclosure is a heterocycle Q of Chemical Formula 1, wherein Y is an element of Q, coordinated with the metal, and Y' is an element of Q and adjacent to Y, connected to the bridge. Therefore, since the present disclosure adopts various neutral ligand units satisfying the above structure, a catalyst having higher activity and higher comonomer incorporation rate than conventional CGC precursors can be prepared.
[0230] Furthermore, an alkyl group or a carboxylate (or salt) may be included as a metal substituent of the metallocene compound represented by Chemical Formula 1, which serves as a good leaving group to promote a reaction with a co-catalyst such as MAO, thereby increasing activity.
[0231] Therefore, when using metallocene compounds, the high melt index of polyethylene can be maintained, the low molecular weight components can be reduced, the molecular weight distribution can be narrower, and the SCB content can be increased to increase the effective number of physical crosslinks of the molecules, thereby preparing polyethylene with reduced total volatile organic compounds (TVOC).
[0232] Specifically, in Chemical Formula 1, M may be zirconium (Zr).
[0233] In addition, in Chemical Formula 1, R1 to R4 may each independently be hydrogen, C 1-10 Alkyl or C 6-20 The aryl group, or R1 and R2 or R3 and R4 may be linked to each other to form a substituted or unsubstituted C 6-20 Preferably, R1 to R4 may each independently be hydrogen or methyl, or R1 and R2 or R3 and R4 may be connected to each other to form a benzene ring or a 1,2,3,4-tetrahydronaphthalene ring, wherein the benzene ring or the 1,2,3,4-tetrahydronaphthalene ring may be unsubstituted or substituted with one to four substituents selected from the group consisting of a methyl group, a tert-butyl group and a 4-tert-butylphenyl group.
[0234] In addition, in Chemical Formula 1, R5 and R6 can each independently be C 1-10 Alkyl or C 6-20 Aryl, or R5 and R6 may be linked to each other to form a C 3-20 Alicyclic or C 6-20 Preferably, R5 and R6 may each independently be a methyl group or a phenyl group, or R5 and R6 may be connected to each other to form a cyclooctane ring.
[0235] More preferably, R5 and R6 may both be phenyl.
[0236] In addition, in Chemical Formula 1, X1 and X2 may each independently be a methyl group or an acetate (or salt).
[0237] In addition, in Chemical Formula 1, when X1 or X2 is -O(CO)R', R' may be specifically a methyl group.
[0238] In addition, in Chemical Formula 1, X1 and X2 may be identical to each other.
[0239] In addition, in Chemical Formula 1, Q may be a substituted or unsubstituted C 2-20 A heterocyclic ring containing at least one selected from the group consisting of N, O and S.
[0240] Preferably, Q may be a pyridine ring, a quinoline ring, a 4,5-dihydrooxazole ring, a pyrazole ring or a benzoxazole ring, wherein Q is unsubstituted or substituted with one to four substituents selected from the group consisting of a methyl group, an isopropyl group and a diphenylamino group.
[0241] More preferably, Q may be a pyridine ring, a 4,5-dihydrooxazole ring, a pyrazole ring or a benzoxazole ring, wherein Q is unsubstituted or substituted with one to four substituents selected from the group consisting of a methyl group, an isopropyl group and a diphenylamino group.
[0242] In addition, in Chemical Formula 1, Y is a hetero atom coordinated to the metal M, and preferably, Y may be N.
[0243] Meanwhile, specific examples of the metallocene compound represented by Chemical Formula 1 may include compounds represented by the following structural formulas, but the present invention is not limited thereto:
[0244]
[0245]
[0246] When X1 and X2 are the same as each other, the metallocene compound represented by Chemical Formula 1 can be prepared by, for example, the preparation method in the following Reaction Scheme 1, but is not limited thereto, and can be prepared according to a known method for preparing an organic compound and a metallocene compound. The preparation method will be implemented in more detail in the preparation examples described later.
[0247] [Reaction Scheme 1]
[0248]
[0249] In Reaction Scheme 1, B, M, R1 to R6, X1, X2, Q, Y and Y are the same as defined in Chemical Formula 1.
[0250] Meanwhile, the catalyst composition for producing the second polyethylene may include the metallocene compound of Chemical Formula 1 as a single catalyst, or may include the metallocene compound together with a carrier and an optional co-catalyst.
[0251] The support may have highly reactive hydroxyl groups, silanol groups or siloxane groups on its surface. The support may be surface modified by calcination, or may be dried to remove moisture from the surface. For example, the support may be silica obtained by calcining silica gel, silica dried at high temperature, silica-alumina, or silica-magnesia, and it may generally contain oxides, carbonates, sulfates or nitrates, such as Na2O, K2CO3, BaSO4, Mg(NO3)2, etc.
[0252] In addition, the cocatalyst can be any cocatalyst used for polymerizing olefins in the presence of a general metallocene catalyst. The cocatalyst allows the formation of a bond between the hydroxyl groups on the support and the Group 13 transition metal. In addition, since the cocatalyst is present only on the surface of the support, it can help ensure the intrinsic properties of the specific mixed catalyst composition of the present disclosure without fouling, adhesion to the wall surface of the reactor or adhesion to each other.
[0253] In addition, when preparing the second polyethylene, a C4-C8 alpha-olefin comonomer is added. The C4 to C8 alpha-olefin is specifically selected from one or more of the group consisting of 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene and 1-octene, or a mixture of two or more types. Preferably, it can be 1-butene or 1-hexene.
[0254] When preparing the second polyethylene, the addition amount of the C4 to C8 α-olefin comonomer may be 0.1 to 10 parts by weight, more specifically 0.1 parts by weight or more, 1 parts by weight or more, 5 parts by weight or more, or 6 parts by weight or more, and 10 parts by weight or less, or 8 parts by weight or less, based on 100 parts by weight of the ethylene monomer. When the above weight ratio condition is met, the physical properties of the above second polyethylene can be more easily achieved.
[0255] Furthermore, the polymerization reaction for producing the second polyethylene is carried out while introducing hydrogen.
[0256] At this time, the input amount of hydrogen can be appropriately adjusted to achieve the physical properties of the above-mentioned second polyethylene. For example, in the present disclosure, based on the total weight of the monomers including ethylene and C4 to C8 alpha olefin comonomers, the input amount of hydrogen can be 0.0001 weight part to 0.05 weight part. When hydrogen is introduced within the above range, the combined physical properties of the above-mentioned polyethylene resin composition can be easily achieved. More specifically, its introduction amount can be more than 0.0001 weight part, more than 0.0005 weight part or more than 0.0007 weight part, and less than 0.05 weight part, less than 0.005 weight part or less than 0.002 weight part.
[0257] In addition, the polymerization reaction for producing the second polyethylene may be performed at a temperature of 70 to 90° C. and a pressure of 5 to 10 bar.
[0258] Furthermore, the preparation method of the present disclosure may further include a step of performing an additional polymerization reaction on unreacted monomers contained in the polymerization product in a post-reactor after the polymerization reaction for producing the second polyethylene.
[0259] At this time, the additional polymerization reaction may be performed under the same reaction conditions as the polymerization reaction, specifically, at a temperature of 70° C. to 90° C. and a pressure of 5 bar to 10 bar.
[0260] Through the above two-step polymerization method, a second polyethylene satisfying the above physical property conditions is obtained.
[0261] The third step is a preparation step of mixing the first polyethylene prepared in the first step with the second polyethylene prepared in the second step to prepare a polyethylene resin composition.
[0262] The first polyethylene and the second polyethylene may be mixed in an appropriate mixing ratio to achieve the physical properties of the polyethylene resin composition. Specifically, the mixing weight ratio of the first polyethylene and the second polyethylene is 90:10 to 70:30.
[0263] In addition, the mixing process is not particularly limited and may be performed according to a conventional mixing process.
[0264] Meanwhile, the preparation method of the present disclosure may further include the step of melt extruding to obtain the mixture after completing the mixing process in the third step.
[0265] The pellet-type polyethylene resin composition can be produced by the above-mentioned melt extrusion step.
[0266] Since the polymer product after the polymerization reaction in the first and second steps is obtained in the form of powder, the types of applicable antioxidants are limited. In addition, since the content of the antioxidant varies greatly depending on the powder, the products manufactured using it vary greatly in their physical properties. In contrast, when the melt extrusion process is performed, the components containing the antioxidant are uniformly mixed, and the resulting products can have uniform physical properties.
[0267] Meanwhile, as used herein, pellets or pellet-type are small particles or flakes formed by extruding raw materials, and include all shapes classified as pellets in the art, including round, flat, thin, polygonal, rod-shaped, etc. The size of the pellets is appropriately determined according to the use and shape, without particular limitation, but the pellets in the present invention are defined as having an average diameter of 2 mm or more to distinguish from powders having a small average diameter of about 1 mm. In this regard, the "diameter" is the longest distance between any straight line distances of the outer circumferential surface of the pellets, and can be measured using an imaging microscope or the like.
[0268] The melt extrusion process can be carried out using a common extruder, and the specific method and conditions are not particularly limited as long as the morphological conditions of the pellets are met.
[0269] In addition, during melt extrusion, one or more additives, such as antioxidants, stabilizers, neutralizers, slip agents, antiblocking agents, UV stabilizers, antistatic agents, etc., may be added within a range that does not deteriorate the physical properties of the polyethylene resin composition. Therefore, the prepared polyethylene resin composition may also include one or more additives, such as antioxidants, neutralizers, slip agents, antiblocking agents, UV stabilizers, and antistatic agents, etc. At the same time, in the present invention, the additives do not affect the physical properties of the polyethylene resin composition, and when the resin composition is used to manufacture products, the processing performance and the quality of the manufactured products can be improved.
[0270] For example, the antioxidant may include phenolic antioxidants, phosphorus antioxidants, amine antioxidants, and the like, and any one of them or a mixture of two or more thereof. Specific examples of antioxidants may include phenolic antioxidants such as tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl-propionate)]methane (CAS 6683-19-8), 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, etc.; phosphorus antioxidants such as tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, etc.; or amine antioxidants such as phenylnaphthylamine, 4,4'-(α,α-dimethylbenzyl)diphenylamine, and N,N'-di-2-naphthyl-p-phenylenediamine, and any one of them or a mixture of two or more thereof may be used. Alternatively, you can use commercially available Irganox TM 1010 (manufactured by BASF), Irganox TM 3114 (manufactured by BASF), Irganox TM 1076 (manufactured by BASF), Irgafos TM 168 (manufactured by BASF), Irgafos TM 626 (manufactured by BASF) or Cyanox TM 1790 (manufactured by CYTEC).
[0271] Wherein, the polyethylene resin composition can include a mixture of a main phenolic antioxidant and a secondary phosphorus antioxidant. In this regard, based on the gross weight of the mixture of the first polyethylene and the second polyethylene, the addition of the main phenolic antioxidant can be more than 50ppm, more than 200ppm or more than 250ppm, and less than 500ppm or less than 300ppm. Based on the gross weight of the mixture of the first polyethylene and the second polyethylene, the addition of the secondary phosphorus antioxidant can be more than 50ppm, more than 200ppm or more than 250ppm, and less than 500ppm or less than 300ppm. Therefore, based on the gross weight of the resin composition, the polyethylene resin composition can include more than 50ppm, more than 200ppm or more than 250ppm, and less than 500ppm or less than 300ppm of the main phenolic antioxidant, and more than 50ppm, more than 200ppm or more than 250ppm, and less than 500ppm or less than 300ppm of the secondary phosphorus antioxidant.
[0272] In addition, stabilizer can be magnesium aluminum hydroxy carbonate (hydrotalcite), aluminum magnesium zinc carbonate hydroxide, aluminum magnesium calcium carbonate hydroxide etc., and any one of these or a mixture of two or more can be used. In addition, commercially available DHT-4A (manufactured by Kyowa Chemical Industries) can be used. Based on the gross weight of the mixture of the first polyethylene and the second polyethylene, the addition of stabilizer can be more than 100ppm, more than 200ppm or more than 300ppm, and less than 1000ppm, less than 700ppm or less than 500ppm. Therefore, based on the gross weight of resin combination, polyethylene resin composition can include more than 100ppm, more than 200ppm or more than 300ppm, and less than 1000ppm, less than 700ppm or less than 500ppm The stabilizer of the amount.
[0273] In addition, neutralizing agent can include calcium stearate (Ca-St), calcium palmitate, zinc stearate, zinc palmitate etc., and any one of them or a mixture of two or more can be used. Based on the gross weight of the mixture of the first polyethylene and the second polyethylene, the addition amount of neutralizing agent can be more than 100ppm, more than 300ppm or more than 500ppm, and less than 1000ppm or less than 700ppm. Therefore, based on the gross weight of resin combination, polyethylene resin composition can include more than 100ppm, more than 300ppm or more than 500ppm, and less than 1000ppm or less than 700ppm of the neutralizing agent of the amount.
[0274] The melt extrusion step can be performed according to a common method, for example, using an extruder (eg, a twin-screw extruder) at an extrusion temperature of 180°C to 220°C or 180°C to 210°C.
[0275] The polyethylene resin composition meeting the above physical property requirements is prepared by the above preparation method.
[0276] The prepared polyethylene resin composition has high mechanical strength and transparency and excellent stretchability. Therefore, when manufacturing a biaxially stretched film, there is no worry about defects such as breakage or shrinkage in the TD stretching process. In addition, the manufactured biaxially stretched film can show excellent stretchability and tensile strength.
[0277] According to the present disclosure, provided are a composition for producing a film comprising the polyethylene resin composition, and a film produced using the polyethylene resin composition, in particular a stretched film.
[0278] The composition for film formation can be prepared in the same manner as a commonly used method for preparing a composition for film formation, except that the above-mentioned polyethylene resin composition is contained.
[0279] In addition, in addition to the above-mentioned polyethylene resin composition, the film-forming composition may further include other polyethylene resin compositions having different compositions or physical properties from the above-mentioned polyethylene resin composition. In this case, the other polyethylene resin composition may be included in a state of being mixed with the above-mentioned polyethylene resin composition, and its content may be appropriately determined according to the purpose and physical properties to be achieved. For example, based on the total weight of the film-forming composition, the content of the other polyethylene resin composition may be greater than 0wt% and less than 40wt%.
[0280] Further, the film may specifically be a stretched film or a biaxially stretched film.
[0281] The film can be produced in the same manner as a common method of producing a film or stretching a film, except that the above-mentioned polyethylene resin composition is included.
[0282] By including the above-mentioned polyethylene resin composition, the film can show excellent stretchability and strength properties. Specifically, the stretch ratio of the film of the present disclosure in the longitudinal direction (MD) can be 4 to 7 times, or 5 to 6 times, and the stretch ratio in the transverse direction (TD) can be 4 to 9 times, or 8 to 9 times.
[0283] In addition, the film may satisfy the following conditions (e1) to (e3):
[0284] (e1) when measured according to ASTM D638 at a thickness of 2 mm, the tensile strength in the MD direction is 100 MPa or more and the tensile strength in the TD direction is 170 MPa or more;
[0285] (e2) a 1% secant modulus of 800 MPa to 1400 MPa in the MD direction and a 1% secant modulus of 1100 MPa to 2300 MPa in the TD direction when measured according to ASTM D882 at a thickness of 2 mm;
[0286] (e3) The haze measured according to ISO 13468 when the film is stretched at a stretching ratio of 5×8 (MD×TD) or more and has a thickness of 20 μm is 30% or less.
[0287] More specifically, when measured according to ASTM D638 at a thickness of 2 mm, the MD tensile strength of the film can be 100 MPa or more, 105 MPa or more, 109 MPa or more, 112 MPa or more, or 114 MPa or more. Because higher tensile strengths are evaluated as better, there is no specific upper limit. For example, the MD tensile strength can be 200 MPa or less, 150 MPa or less, 130 MPa or less, 125 MPa or less, or 122 MPa or less.
[0288] In addition, when measured according to ASTM D638 at a thickness of 2 mm, the TD tensile strength of the film can be more than 170 MPa, more than 175 MPa, more than 178 MPa, more than 179 MPa, or more than 180 MPa. Because higher tensile strength is evaluated as better, there is no specific upper limit. For example, the TD tensile strength can be less than 300 MPa, less than 200 MPa, less than 190 MPa, less than 185 MPa, or less than 182 MPa.
[0289] In addition, when measured according to ASTM D882 at a thickness of 2 mm, the 1% secant modulus of the film in the MD direction can be 800 MPa or more, 805 MPa or more, 175 MPa or more, 178 MPa or more, 179 MPa or more, or 180 MPa or more. Because higher tensile strength is evaluated to be better, there is no specific upper limit. For example, the TD tensile strength can be 300 MPa or less, 200 MPa or less, 190 MPa or less, 185 MPa or less, or 182 MPa or less.
[0290] In addition, when stretched at a stretching ratio of 5×8 (MD×TD) or more and having a thickness of 20 μm, the haze of the film measured according to ISO13468 standard may be 30% or less, 15% or less, 10% or less, 8% or less, 5% or less, 4% or less, 3% or less, 2% or less, or 1% or less. Since lower haze is evaluated as better, there is no specific lower limit. For example, the haze may be 0% or more, or 0.1% or more.
[0291] Hereinafter, preferred exemplary embodiments will be provided to better understand the present invention. However, the following exemplary embodiments are only used to more easily understand the present invention, but the content of the present invention is not limited thereto.
[0292] <Preparation of Catalyst>
[0293] Synthesis Example 1 (Ziegler-Natta catalyst for preparing polymer A)
[0294] 34 g of anhydrous magnesium chloride (99 wt % or more, moisture content less than 1%) was placed in a 2-liter Buchi reactor dried with nitrogen, and 600 ml of purified hexane with a moisture content less than 0.5 ppm was also placed in the reactor. Under stirring, 175 ml of anhydrous 2-ethyl-1-hexanol was added to the resulting reaction product, and then stirred at a temperature of 130° C. for about 2 hours to obtain a uniform magnesium carrier solution.
[0295] While stirring the homogeneous solution at a temperature of 35°C and a speed of 200 rpm, 200 ml of TiCl4 was slowly added over 1 hour and stirred for another 1 hour. In the process, a solid material was produced. After the solid matter was precipitated, the liquid portion was removed and the separated solid matter was washed several times with hexane until the titanium concentration in the washing liquid was less than 0.5 mmol. To the washed solid matter, purified hexane was added to a total volume of 1 liter. The titanium concentration in the resulting hexane slurry was 30 mM. 7 ml of chlorocyclohexane was added to the hexane slurry at a temperature of 40°C and stirred for 1 hour to obtain a Ziegler-Natta catalyst supported on magnesium.
[0296] The prepared catalyst contains TiCl4 as a main catalyst, and also contains chlorocyclohexane at a molar ratio of 0.13 based on 1 mol of the main catalyst. In addition, the molar ratio of Mg:Ti in the catalyst is 4:1, and the average particle size of the catalyst particles is 8 μm.
[0297] Synthesis Example 2 (Metallocene Catalyst for Preparing Polymer B)
[0298] Step 1: Preparation of catalyst precursor
[0299]
[0300] 2-Bromopyridine (1 equivalent) was dissolved in tetrahydrofuran (0.1 M). Then n-butyllithium (1 equivalent) was slowly added dropwise at -90°C and then stirred at the same temperature for 1 hour. Then, chlorodiphenylborane (1 equivalent) was dissolved in toluene (0.3 M) and then slowly added dropwise to the first reaction product at -78°C and then stirred for 1 hour. Thereafter, the mixture was stirred at room temperature for 12 hours, the solvent was dried under vacuum, toluene was added, and the filtrate obtained by removing the solids through a filter was dried under vacuum to obtain diphenyl(pyridin-2-yl)borane.
[0301] Diphenyl(pyridin-2-yl)borane (1 equivalent) was dissolved in tetrahydrofuran (0.1 M), and then a solution of tetramethylcyclopentadienyl lithium (Li(CpMe4), 1 equivalent) dissolved in tetrahydrofuran (0.1 M) was slowly added dropwise at 0°C, and then stirred at room temperature overnight. The solvent was dried under vacuum, and toluene / ether (volume ratio of 3 / 1, 0.3 M) was introduced to dissolve, and MCl4 (1 equivalent) was mixed with toluene (0.2 M), and then introduced at -78°C, and then stirred at room temperature overnight. When the reaction was complete, the solvent was dried under vacuum, and dichloromethane was introduced and the salt was removed by filtering. The filtrate was dried under vacuum, and then dichloromethane / hexane was added for recrystallization. The resulting solid was filtered and dried under vacuum to obtain dichloro{biphenyl(pyridin-2-yl-κN)(η 5 -2,3,4,5-tetramethylcyclopentadien-2,4-dien-1-ylidene)boronic acid}zirconium(IV).
[0302] Dichloro{biphenyl(pyridin-2-yl-κN)(η 5 -2,3,4,5-tetramethylcyclopentane-2,4-diene-1-ylidene) borate} zirconium (IV) (1 equivalent) was dissolved in toluene / ether (volume ratio of 3 / 1, 0.3M), and then a solution of methyl lithium (2 equivalents) dissolved in hexane or ether was slowly added dropwise at -78°C, followed by stirring at room temperature for 12 hours. When the reaction was complete, the solvent was dried under vacuum, and dichloromethane was introduced and the salt was removed by a filter. The filtrate was dried under vacuum, and then dichloromethane / hexane was added for recrystallization. The resulting solid was filtered and dried under vacuum to obtain the precursor compound (1a).
[0303] 1 H NMR (500MHz, CDCl3, ppm): δ8.32(d,1H),8.05(d,4H),7.70(t,1H),7.42(t,1H ),7.40(t,4H),7.23(d,1H),7.17(t,2H),2.08(s,6H),1.93(s,6H)0.95(s,6H)
[0304] Step 2: Preparation of catalyst
[0305] Add 50mL of toluene to the microreactor. Then add 7g of silica gel (SYLOPOL952X, calcined at 250°C) under Ar, then slowly inject methylaluminoxane (MAO) 8.5mmol / g-SiO2 at room temperature, and react for 24 hours at 95°C under stirring. After the reaction is completed, the solution is cooled to room temperature, left for 15 minutes, and the solvent is decanted using a cannula. Add toluene (400mL), stir for 1 minute and let stand for 15 minutes, then use a cannula to decant the solvent.
[0306] The catalyst precursor compound (1a) prepared in 60 μmol step 1 is dissolved in 30 mL toluene, transferred to the reactor with a sleeve, and stirred for 2 hours at 80 ° C. When the reaction is complete and the precipitation is complete, the solution is cooled to room temperature and placed for 15 minutes, and the solvent is decanted using a sleeve. The supernatant is removed and the remaining reaction product is washed with toluene. After washing with hexane again, 2 wt % of N, N-bis (2-hydroxyethyl) pentadecylamine (Atmer 163) is dissolved in 3 mL of hexane as an antistatic agent based on the weight (g) of silica, and then stirred at room temperature for 10 minutes. When the reaction is complete and the precipitation is complete, the supernatant is removed, and the remaining product is transferred to a glass filter to remove the solvent.
[0307] Primary drying was performed at room temperature under vacuum for 5 hours, and secondary drying was performed at 45° C. under vacuum for 4 hours to obtain a silica-supported metallocene catalyst in the form of solid particles.
[0308] <Preparation of First Polyethylene>
[0309] Preparation Example 1-1 (Preparation of Polymer A1)
[0310] The polyethylene was produced by using two 100 L continuously stirred tank reactors (CSTRs) and a post reactor in a bimodal slurry process in the presence of a Ziegler-Natta catalyst system.
[0311] Specifically, the first polyethylene was prepared as follows: a catalyst slurry (in which 12.7 g of the Ziegler-Natta catalyst prepared in Synthesis Example 1 was dispersed in each 1 L of hexane), 18 kg / hr of hexane, 5.5 kg / hr of ethylene, and 160 ml / hr (concentration 300 mM) of triethylaluminum (TEAL) were added to the first reactor, and then a polymerization reaction was performed. At this time, the temperature, pressure, and residence time of the reactants in the first reactor were maintained at 80° C., 6 bar, and 5.0 hours, respectively. While maintaining a constant liquid level in the reactor, a slurry mixture containing a polymer formed as a result of the polymerization reaction was continuously transferred to a second reactor connected in series with the first reactor.
[0312] When the slurry mixture containing the polymer prepared in the first reactor is transferred to the second reactor, 19 kg / hr hexane, 4.5 kg / hr ethylene and 55 ml / hr (concentration 300 mM) triethylaluminum (TEAL) are injected into the second reactor, followed by a secondary polymerization reaction to prepare a second polyethylene. At this time, the temperature, pressure and residence time of the reactants in the second reactor are maintained at 75° C., 2 bar and 2.4 hours, respectively. While maintaining a constant liquid level in the reactor, the polymer mixture formed as a result of the polymerization reaction is continuously transferred to a post-reactor connected in series with the second reactor.
[0313] The temperature in the post-reactor was maintained at 78° C. In the post-reactor, unreacted monomers in the polymer mixture transferred from the second reactor were polymerized. The obtained polymer product was subjected to solvent removal and drying processes to obtain an ethylene homopolymer (A1) as the first polyethylene.
[0314] Preparation Example 1-2 (Preparation of Polymer A2)
[0315] An ethylene / 1-butene copolymer (A2) was prepared as a first polyethylene in the same manner as in Preparation Example 1-1, except that 4 ml / min of 1-butene was additionally injected into the second reactor.
[0316] Preparation Example 1-2 (Preparation of Polymer A3)
[0317] An ethylene / 1-butene copolymer (A3) was prepared as the first polyethylene in the same manner as in Preparation Example 1-1, except that 7 g / hr of hydrogen was injected into the first reactor and 4 ml / min of 1-butene was additionally injected into the second reactor.
[0318] <Preparation of Second Polyethylene>
[0319] Preparation Example 2-1 (Preparation of Polymer B1)
[0320] The second polyethylene is prepared by polymerization in the presence of a metallocene catalyst system using a single polymerization reactor and a post-reactor.
[0321] In detail, 145 ml / hr of catalyst slurry (wherein 6.5 g of the metallocene catalyst prepared in Synthesis Example 2 was dispersed in 1 L of hexane), 18 kg / hr of hexane, 10 kg / hr of ethylene, 0.1 g / hr of hydrogen, 0.6 kg / hr of 1-hexene and 20 ml / hr (concentration 300 mM) of triethylaluminum (TEAL)) were injected into the polymerization reactor, followed by polymerization. At this time, the temperature, pressure and residence time of the reactants in the polymerization reactor were maintained at 70° C., 7 bar and 3.0 hours, respectively. When the polymerization was completed, the prepared slurry containing the polymer was transferred to the post-reactor.
[0322] The temperature in the post-reactor was maintained at 70° C. In the post-reactor, unreacted monomers in the slurry containing the polymer prepared in the above polymerization reactor were polymerized. The obtained polymer product was subjected to solvent removal and drying processes to obtain an ethylene / 1-hexene copolymer (B1) as the second polyethylene.
[0323] Preparation Example 2-2 (Preparation of Polymer B2)
[0324] An ethylene / 1-octene copolymer (B2) was prepared as a second polyethylene in the same manner as in Preparation Example 2-2, except that 0.6 kg / hr of 1-octene instead of 1-hexene and 0.15 g / hr of hydrogen were injected into the polymerization reactor.
[0325] Experimental Example 1
[0326] The physical properties of the first and second polyethylenes prepared in Preparation Example were evaluated by the following methods, and the results are shown in Table 1 below.
[0327] (1) Melt index (MI) 2.16 )[g / 10min]
[0328] The melt index (MI) was measured at 190°C under a load of 2.16 kg according to ASTM D1238. 2.16 ).
[0329] (2) MFRR(MI 21.6 / MI 2.16 )
[0330] Melt Index (MI 21.6 ) is measured at 190°C under a load of 21.6 kg according to ASTM D1238, and MFRR (MI 21.6 / MI 2.16 ) by using MI 21.6 (190℃, 21.6kg load) divided by the MI measured above 2.16 (190°C, 2.16 kg load) to obtain.
[0331] (3) Density [g / cm 3 ]
[0332] Density was measured according to ASTM D792 standard.
[0333] (4) Weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn)
[0334] The polyethylene prepared in the preparation example was subjected to gel permeation chromatography (GPC) analysis to determine the weight average molecular weight (Mw) and number average molecular weight (Mn), respectively. The weight average molecular weight determined above was divided by the number average molecular weight to obtain the molecular weight distribution (Mw / Mn).
[0335] Specifically, a Polymer Laboratories PLgel MIX-B 300mm long column was used, and a PL-GPC220 manufactured by Waters was used as a gel permeation chromatography (GPC) instrument. At this time, the evaluation temperature was 160°C, 1,2,4-trichlorobenzene was used as a solvent, and the flow rate was 1mL / min. The polyethylene sample was dissolved in 1,4-trichlorobenzene containing 0.025% BHT at 160°C for 4 hours using a GPC analyzer (PL-GP220) for pretreatment, and prepared to a concentration of 20mg / 10mL, and then fed in an amount of 200μL. Mw and Mn were obtained using a calibration curve formed using a polystyrene standard sample. Nine kinds of polystyrene standard samples having weight average molecular weights (g / mol) of 2,000 / 10,000 / 30,000 / 70,000 / 200,000 / 700,000 / 2,000,000 / 4,000,000 / 10,000,000 were used.
[0336] [Table 1]
[0337]
[0338] In Table 1 above, k represents 'x10 3 '.
[0339] <Preparation of Polyethylene Resin Composition>
[0340] Examples 1 to 18 and Comparative Examples 1 to 17
[0341] Polyethylene resin compositions were prepared by mixing the first and second polyethylenes prepared in the above-mentioned Preparation Examples at various weight ratios.
[0342] Specifically, after mixing the first and second polyethylenes at a weight ratio shown in Table 2 or Table 3, 300 ppm of DHT-4A (magnesium aluminum hydroxycarbonate) manufactured by Kyowa Chemical Industries as a stabilizer, 300 ppm of Irganox 1010 manufactured by BASF as a first antioxidant, and 300 ppm of Irgafos 168 manufactured by BASF as a second antioxidant were added and mixed based on the total weight of the resulting mixture. Then, extrusion was performed at an extrusion temperature of 190° C. using a twin-screw extruder (TEK 30MHS, manufactured by SMPLATECH, with a diameter of 32 pi, L / D=40) to prepare a pellet-type polyethylene resin composition.
[0343] Comparative Examples 18 to 22
[0344] A polyethylene resin composition was prepared as follows: First and second polyethylenes were mixed under the following conditions in the same manner as in Example 1, except that they were mixed in the weight ratio shown in Table 3.
[0345] <First Polyethylene>
[0346] A4:MI 2.16 =50g / 10min and density =0.965g / cm 3 Polyethylene
[0347] A5:MI 2.16 =5.1g / 10min and density =0.961g / cm 3 Polyethylene
[0348] <Second Polyethylene>
[0349] B3:MI 2.16 =0.4g / 10min and density =0.940g / cm 3 Polyethylene
[0350] B4:MI 2.16 =3.5g / 10min and density = 0.904g / cm 3 Polyethylene
[0351] B5:MI 2.16 =1.0g / 10min and density =0.905g / cm 3 Polyethylene
[0352] B6:MI 21.6 =3.5g / 10min and density = 0.940g / cm 3 Polyethylene (TL2000, manufactured by LG Chem)
[0353] Comparative Example 23
[0354] Use LUTENE-H PE0235 manufactured by LG Chem as the polyethylene resin composition.
[0355] Comparative Example 24
[0356] Use LUTENE-H ME5500 manufactured by LG Chem as the polyethylene resin composition.
[0357] [Table 2]
[0358]
[0359] [Table 3]
[0360]
[0361] Experimental Example 2
[0362] The polyethylene resin compositions of the examples and comparative examples were subjected to temperature rising elution fractionation (TREF) analysis in the following manner to obtain the content ratio of the polymer fractions eluted in each temperature range.
[0363] Specifically, a 30 mg polyethylene resin composition sample was introduced into a TREF device (manufactured by PolymerChar), then dissolved in 20 mL of trichlorobenzene at 150 °C for 60 minutes, and then stabilized at 140 °C for 20 minutes. Thereafter, it was cooled to 35 °C at a cooling rate of 0.5 °C / min and held for 10 minutes. Then, the solvent trichlorobenzene was applied to the column at a flow rate of 0.5 mL / min while heating from 35 °C to 140 °C at a heating rate of 1 °C / min, and then the concentration of the eluted polymer was measured. Other measurement conditions are as follows. From the measurement results, a TREF analysis curve with the x-axis being the elution temperature (Te) (°C) and the y-axis being the elution amount (dw / dt) was obtained.
[0364] <TREF Measurement Conditions>
[0365] Dissolution rate: 40 °C / min
[0366] Stabilization rate: 40 °C / min
[0367] Crystallization rate: 0.5 °C / min
[0368] Elution rate: 1 °C / min
[0369] Cleaning rate: 30 °C / min
[0370] Dissolution temperature: 150 °C
[0371] Stabilization temperature: 140 °C
[0372] Crystallization temperature: 35℃
[0373] Elution initial temperature: 35°C
[0374] Elution temperature: 140°C
[0375] Temperature after elution: 150℃
[0376] Cleaning temperature: 150℃
[0377] Dissolution time: 60min
[0378] Stabilization time: 20min
[0379] Crystallization time: 10min
[0380] Pre-injection time: 10min
[0381] Soluble fraction time: 10 min
[0382] Elution time: 10min
[0383] Cleaning time: 10min
[0384] Cleaning cycles: 1
[0385] The content ratio of the fraction eluted in each elution temperature range was calculated as a percentage (wt%) based on the total weight of all eluted fractions obtained by TREF analysis. The results are shown in Tables 4 and 5 below.
[0386] In addition, the results of temperature rising elution fractionation (TREF) analysis of the polyethylene resin compositions of Examples 5 and 6 and Comparative Examples 10 and 14 are shown in Figure 1 middle.
[0387] [Table 4]
[0388] Example No. 25℃-90℃ 40℃-70℃ 90℃-120℃ 100℃-105℃ 1 25.3 2.7 74.7 44.2 2 30.8 8.7 69.2 40.9 3 36.2 14.7 63.8 37.5 4 26.4 3.9 73.6 43.5 5 31.0 8.9 69.0 40.7 6 34.9 13.2 65.1 38.3 7 29.0 6.8 71.0 41.9 8 34.1 12.3 65.9 38.9 9 39.1 17.8 60.9 35.8 10 30.0 7.9 70.0 41.3 11 34.4 12.7 65.6 38.7 12 42.4 21.4 57.6 33.8 13 32.7 10.8 67.3 39.7 14 37.3 15.9 62.7 36.9 15 42.3 21.0 57.7 34.0 16 32.0 10.1 68.0 40.1 17 39.5 18.3 60.5 35.5 18 45.2 24.6 54.8 32.0
[0389] [Table 5]
[0390] Comparative Example No. 25℃-90℃ 40℃-70℃ 90℃-120℃ 100℃-105℃ 1 19.8 0.3 80.2 47.5 2 23.9 1.2 76.1 45.0 3 28.0 5.7 72.0 42.5 4 74.4 56.6 25.6 14.2 5 85.4 68.5 14.6 7.5 6 22.6 0.3 77.4 45.9 7 39.0 17.7 61.0 35.9 8 23.0 0.3 77.0 45.5 9 42.8 21.9 57.2 33.5 10 26.5 4.0 73.5 43.5 11 41.6 20.6 58.4 34.2 12 27.0 4.6 73.0 43.2 13 45.4 24.8 54.6 31.9 14 30.4 8.2 69.6 41.1 15 44.3 23.5 55.7 32.6 16 30.9 8.8 69.1 40.8 17 48.1 27.7 51.9 30.3 18 17.1 0.1 82.9 49.2 19 27.3 5.0 72.7 42.9 20 23.5 0.8 76.5 45.3 21 23.4 0.6 76.6 45.4 22 18.9 0.1 81.1 48.0 23 29.4 7.2 70.6 41.7 24 28.0 5.7 72.0 42.5
[0391] In Tables 4 and 5 above, the temperature range "-" includes the lower limit and the upper limit of the numerical range. For example, 25°C-90°C means a range of 25°C or more and 90°C or less.
[0392] Experimental Example 3
[0393] The physical properties of the polyethylene resin compositions prepared in Examples and Comparative Examples were evaluated by the following methods, and the results are shown in Tables 6 and 7 below.
[0394] (1) Density: Density was measured at 23° C. according to ASTM D792.
[0395] (2) Melt index (MI) 2.16 ): According to ASTM D1238, the melt index (MI) was measured at 190°C under a load of 2.16 kg. 2.16 ).
[0396] (3) MFRR(MI 21.6 / MI 2.16 )
[0397] Melt Index (MI 21.6 ) is measured at 190°C under a load of 21.6 kg according to ASTM D1238, and MFRR (MI 21.6 / MI 2.16 ) by using MI 21.6 (190℃, 21.6kg load) divided by the MI measured above 2.16 (190°C, 2.16 kg load) to obtain.
[0398] (4) Weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn)
[0399] The polyethylene resin compositions prepared in the examples and comparative examples were subjected to gel permeation chromatography (GPC) analysis to determine the weight average molecular weight (Mw) and number average molecular weight (Mn), respectively. The molecular weight distribution (Mw / Mn) was obtained by dividing the above-determined weight average molecular weight by the number average molecular weight.
[0400] In detail, a Polymer Laboratories PLgel MIX-B 300mm long column was used, and a PL-GPC220 manufactured by Waters was used as a gel permeation chromatography (GPC) instrument. At this time, the evaluation temperature was 160°C, 1,2,4-trichlorobenzene was used as a solvent, and the flow rate was 1mL / min. The polyethylene resin composition sample was dissolved in 1,4-trichlorobenzene containing 0.025% BHT at 160°C for 4 hours using a GPC analyzer (PL-GP220) for pretreatment, and prepared to a concentration of 20mg / 10mL, and then fed in an amount of 200μL. Mw and Mn were obtained using a calibration curve formed using a polystyrene standard sample. Nine kinds of polystyrene standard samples having weight average molecular weights (g / mol) of 2,000 / 10,000 / 30,000 / 70,000 / 200,000 / 700,000 / 2,000,000 / 4,000,000 / 10,000,000 were used.
[0401] Furthermore, through GPC analysis, a molecular weight distribution curve with the x-axis being the logarithmic value (logMw) of the weight average molecular weight (Mw; g / mol) and the y-axis being the molecular weight distribution relative to the log value (dwt / dlogMw) was plotted, and the shape of the molecular weight distribution curve was identified.
[0402] (5) Relaxation time (λ; seconds) and shear thinning index
[0403] The viscosity of the polyethylene resin composition was measured using a rotational rheometer at a temperature of 190° C. and an angular frequency of 0.01 Hz to 100 Hz under a strain of 0.5%, and then calculated using the Carreau-Yasuda model of Formula 1 below to determine the relaxation time (λ; seconds) and shear thinning index of the polyethylene.
[0404] Specifically, the samples were prepared by compression molding the polyethylene resin compositions of Examples and Comparative Examples at 190° C. under a nitrogen atmosphere using 25 mm diameter plates (gap between plates: 1.2 mm). Then, an oscillatory shear test was performed on the samples by continuously applying strain (0.5%) at a temperature of 190° C. and an angular frequency of 0.01 Hz to 100 Hz (equivalent to 0.0628 rad / s to 628 rad / s) in the linear viscosity range using DHR-2 manufactured by TA-Instrument. Five measurement points were obtained for every 10 units.
[0405] The viscosity was measured by an oscillatory shear experiment, and a log-log plot was obtained with the x-axis being the angular frequency (Hz) and the y-axis being the viscosity η (Pa·s) of the polyethylene resin composition measured as above. Afterwards, the log-log plot was fitted to the Carreau-Yasuda model represented by Formula 1 to determine the relaxation time (λ; seconds) and the shear thinning index as well as the zero shear viscosity (η0; Pa·s) and the parameter a. In this experimental example, the zero shear viscosity (η0), the parameter a, the relaxation time (λ) and the shear thinning index were calculated using the TRIOS program from TA Instruments, respectively.
[0406] [Equation 1]
[0407]
[0408] In equation 1,
[0409] η is the viscosity of the polyethylene resin composition measured above (Pa·s), and
[0410] η0 is zero shear viscosity (Pa·s), which is the viscosity in a region where the viscosity does not change when the angular frequency approaches zero. In the present disclosure, the zero shear viscosity can be determined by fitting a log-log plot of the angular frequency (unit: Hz) on the x-axis and the viscosity η (unit: Pa·s) of the polyethylene resin composition measured as above on the y-axis to the Carreau-Yasuda model represented by Formula 1.
[0411] in addition, represents the shear rate applied to the polyethylene resin composition, which is the same as the angular frequency converted into rad / s according to the Cox-Merz rule.
[0412] λ is the relaxation time (seconds) of the polyethylene resin composition and can be determined by fitting a log-log plot of angular frequency (Hz) on the x-axis and viscosity η (Pa·s) of the polyethylene resin composition measured as above on the y-axis to the Carreau-Yasuda model represented by Formula 1.
[0413] In addition, n is a shear thinning index and can be determined by fitting a log-log plot of angular frequency (Hz) on the x-axis and viscosity η (Pa·s) of the polyethylene resin composition measured above on the y-axis to the Carreau-Yasuda model represented by Formula 1.
[0414] a is a shape parameter for transition from a Newtonian plateau to a power law region, and can be determined by fitting a log-log plot of angular frequency (Hz) on the x-axis and viscosity η (Pa·s) of the polyethylene resin composition measured as above on the y-axis to a Carreau-Yasuda model represented by Formula 1.
[0415] [Table 6]
[0416]
[0417] [Table 7]
[0418]
[0419] In the above table, N / A means that the measurement was not performed.
[0420] Experimental Example 4
[0421] The stretchability and film properties of stretched films produced using the polyethylene resin compositions prepared in Examples and Comparative Examples were evaluated in the following manner.
[0422] (1) Preparation of cast film and biaxially stretched film
[0423] Cast sheets of the polyethylene resin compositions prepared in Examples and Comparative Examples were prepared using a Bruckner's Lab extruder line (L / D ratio: 42, screw diameter: 25 mm, melt / T-die temperature: 250° C.) with a thickness of 0.72 mm.
[0424] The cast sheet prepared above was subjected to biaxial stretching using a Lab Stretcher KARO 5.0 machine manufactured by Brukner to produce a polyethylene film having a width x height of 90 mm x 90 mm. At this time, after preheating at 110° C. to 130° C. for 60 seconds, stretching (MD→TD) was performed in sequence, and stretching was performed at 300% / s.
[0425] The final film thickness was 20 μm and the stretching ratio was 5×8 times.
[0426] However, the polyethylene resin compositions of Comparative Examples 1, 6, 8 and 19 could not be stretched, and thus could not produce biaxially stretched films.
[0427] <Stretched Film Manufacturing Conditions>
[0428] Sample size: 90mm×90mm
[0429] Stretching Overview: Sequence
[0430] Stretch ratio: 5×8
[0431] Stretching speed: 100% / s to 400% / s
[0432] Stretching temperature: 110℃ to 130℃
[0433] Preheating: 60s
[0434] (2) Maximum stretching ratio
[0435] For the cast film produced in (1), the maximum stretching ratio that can be stretched without breaking or causing defects in the biaxial stretching process was measured in terms of MD×TD using a Lab Stretcher KARO 5.0 machine manufactured by Brukner.
[0436] <Measurement conditions>
[0437] Sample size: 90mm×90mm
[0438] Stretching Overview: Sequence
[0439] Stretching ratio: 5 to 6 times in MD, 4 to 9 times in TD
[0440] Stretching speed: 100% / s to 400% / s
[0441] Stretching temperature: 110℃ to 130℃
[0442] Preheating temperature: 100s
[0443] (3) Toughness
[0444] Toughness was measured according to ASTM D638 standard.
[0445] Specifically, according to the ASTM D638 standard, the polyethylene resin composition of the embodiment and the comparative example was hot pressed at 190°C to form a sheet with a thickness of 2 mm, which was then cut into PE samples. The PE sample prepared in this way was fixed horizontally to a Zwick tensile tester (UTM), and the tensile test was performed at room temperature (23±5°C) by pulling the above PE sheet in the MD or TD direction. The tensile strength measured at a pulling speed of 50 mm / min is expressed as toughness in [MPa]. MD tensile strengths above 100 MPa and TD tensile strengths above 170 MPa are considered to be excellent.
[0446] (4) Stiffness
[0447] Stiffness was measured according to ASTM D882.
[0448] Specifically, the polyethylene resin composition of the embodiment and the comparative example was hot pressed at 190°C to form a sheet with a thickness of 2 mm according to the ASTM D882 standard, and then cut into PE samples. The PE sample prepared in this way was fixed horizontally to a Zwick tensile tester (UTM), and a tensile test was performed at room temperature (23 ± 5°C) by pulling the above PE sheet. The 1% secant modulus (also called elastic modulus) measured at a pulling speed of 5 mm / min is expressed as stiffness in [MPa]. 1% secant modulus or stiffness above 800 MPa in MD and TD directions is considered to be excellent.
[0449] (5) Transparency
[0450] The haze [%] of the biaxially stretched film produced in (1) was measured according to ISO 13468. Lower haze values indicate better transparency, and generally, haze values of 30% or less are considered excellent.
[0451] [Table 8]
[0452]
[0453] [Table 9]
[0454]
[0455] In the above table, N / A means that no measurement was performed.
[0456] When a stretched film was produced using the polyethylene resin composition of the Examples, it was confirmed that the film exhibited excellent stretch ratio characteristics, as well as improved mechanical properties and transparency.
[0457] On the other hand, since the polyethylene resin compositions of Comparative Examples 1, 6, 8 and 18 had high density, stretching was impossible and no stretched films could be produced.
[0458] In addition, in the case of Comparative Examples 4 and 5 containing only low-density polyethylene, the film exhibited excellent transparency due to the low-density characteristics of the resin composition. However, TREF analysis showed that the content of the fraction eluted in the low-temperature region was high and the content of the fraction eluted in the high-temperature region was low, resulting in a significant decrease in stiffness in the MD and TD directions.
[0459] Meanwhile, in the case of Comparative Examples 14 and 16, which comprise a mixture of low-density polyethylene and high-density polyethylene but have a high content of the high-density first polyethylene and a low content of the low-density second polyethylene, toughness and transparency characteristics are greatly reduced due to excessively broad molecular weight distribution. In the case of Comparative Examples 7, 9, 11, 13, 15, and 17, in which the content of the high-density first polyethylene is low and the content of the low-density polyethylene is high, although transparency is excellent, TD tensile strength and stiffness are greatly reduced during film production due to low MFRR or low density.
[0460] In addition, in the case of Comparative Examples 2, 3, 10 and 12 having a broad molecular weight distribution and a high MFRR, tensile properties, toughness in the MD and TD directions, and transparency were reduced, and the reduction in transparency was particularly significant.
[0461] In the case of Comparative Examples 19 to 21, high MI and MFRR made it difficult to produce a cast sheet, and the stretchability during film production was poor. In addition, due to the wide molecular weight distribution, the TD tensile strength of the produced film was reduced and the transparency was reduced.
[0462] In the case of Comparative Example 22, excessively high MI and MFRR resulted in a processing viscosity too low to produce a cast sheet with a consistent thickness. In addition, the content of the fraction eluted in the low temperature region in the TREF analysis was low, resulting in poor stretchability in film production.
[0463] Furthermore, Comparative Example 23 exhibited poor stretchability in film production due to low MI and high viscosity characteristics, and Comparative Example 24 exhibited poor stretchability in film production due to high MI and low viscosity characteristics.
Claims
1. A polyethylene resin composition, which satisfies the following conditions (a1) to (a5): (a1) MI measured according to ASTM D1238 at 190°C and 2.16 kg 2.16 : 0.5g / 10min to 3.0g / 10min, (a2) Density measured according to ASTM D792: 0.940 g / cm 3 Up to 0.955g / cm 3 , (a3) MFRR(MI 21.6 / MI 2.16 ): 60 or more and less than 80, (a4) Molecular weight distribution (Mw / Mn): 10 to 14, (a5) In a temperature rising elution fractionation (TREF) analysis, based on the total weight of all eluted fractions, Content of the polymer fraction eluted in the range of 25°C to 90°C: 20 wt% to 50 wt%, and Content of the polymer fraction eluted in the range of 90°C to 120°C: 50 wt% to 80 wt%.
2. The polyethylene resin composition according to claim 1, wherein The polyethylene resin composition satisfies the following conditions in temperature rising elution fractionation (TREF) analysis: Based on the total weight of all eluted fractions, Content of the polymer fraction eluted in the range of 40°C to 70°C: 1 wt% to 30 wt%; and Content of the polymer fraction eluted in the range of 100°C to 105°C: 30 wt% to 45 wt%.
3. The polyethylene resin composition according to claim 1, wherein The polyethylene resin composition further satisfies one or more of the following conditions (b1) to (b3): (b1) weight average molecular weight (Mw): 100000 g / mol to 160000 g / mol, (b2) Relaxation time: 0.1 s to 0.9 s, (b3) Shear thinning index: 0.2 to 0.
5.
4. The polyethylene resin composition according to claim 1, wherein The polyethylene resin composition comprises, in a weight ratio of 90:10 to 70:30: Density measured according to ASTM D792 is 0.950 g / cm 3 MI measured above and according to ASTM D1238 at 190°C and 2.16 kg 2.16 The first polyethylene is 0.5 g / 10 min to 2 g / 10 min; and Density measured according to ASTM D792 is 0.925 g / cm 3 MI measured at 190°C and 2.16 kg according to ASTM D1238 2.16 The second polyethylene is 1 g / 10 min to 5 g / 10 min.
5. The polyethylene resin composition according to claim 4, wherein The first polyethylene also satisfies the following conditions (c1) to (c5): (c1) Density measured according to ASTM D792: 0.950 g / cm 3 Up to 0.965g / cm 3 , (c2) MI measured according to ASTM D1238 at 190°C and 2.16 kg 2.16 :0.5g / 10min to 2g / 10min, (c3) MFRR(MI 21.6 / MI 2.16 ): 50 to 100, (c4) weight average molecular weight (Mw): 130000 g / mol to 160000 g / mol, (c5) Molecular weight distribution (Mw / Mn): 10 to 16.
6. The polyethylene resin composition according to claim 4, wherein The first polyethylene is one or more of an ethylene homopolymer and an ethylene / C4-C8 alpha olefin copolymer.
7. The polyethylene resin composition according to claim 4, wherein The second polyethylene satisfies the following conditions (d1) to (d5): (d1) Density measured according to ASTM D792: 0.910 g / cm 3 Up to 0.925g / cm 3 , (d2) MI measured according to ASTM D1238 at 190°C and 2.16 kg 2.16 :1g / 10min to 5g / 10min, (d3)MFRR(MI 21.6 / MI 2.16 ): 10 to 50, (d4) weight average molecular weight (Mw): 50000 g / mol to 130000 g / mol, (d5) Molecular weight distribution (Mw / Mn): 1 to 10.
8. The polyethylene resin composition according to claim 4, wherein The second polyethylene is an ethylene / C4-C8 alpha olefin copolymer.
9. The method for preparing the polyethylene resin composition according to claim 1, comprising: The first step is to carry out a primary polymerization reaction of ethylene in a first reactor in the presence of a Ziegler-Natta catalyst, transfer the obtained polymerization product to a second reactor, and add one or more ethylene and C4-C8 alpha olefins to carry out a secondary polymerization reaction, thereby preparing a first polyethylene; The second step is to prepare a second polyethylene by polymerizing ethylene and C4-C8 α-olefin in the presence of a catalyst in another single reactor while introducing hydrogen, wherein the catalyst comprises a metallocene compound represented by the following Chemical Formula 1; and The third step is to mix the first polyethylene and the second polyethylene in a weight ratio of 90:10 to 70:30; [Chemical formula 1] In Chemical Formula 1, B is boron, M is a Group 4 transition metal, R1 to R4 are each independently hydrogen, C 1-20 Alkyl, C 3-20 Cycloalkyl or C 6-20 aryl, or R1 and R2, or R3 and R4 are connected to each other to form a substituted or unsubstituted C 6-60 Aromatic rings, R5 and R6 are each independently C 1-20 Alkyl, C 3-20 Cycloalkyl or C 6-20 Aryl, or R5 and R6 are connected to each other to form a C 3-60 Alicyclic or C 6-60 Aromatic rings, X1 and X2 are each independently C 1-20 Alkyl or -O(CO)R', where R' is C 1-20 alkyl, Q is substituted or unsubstituted C 2-60 a heterocyclic ring comprising at least one selected from the group consisting of N, O and S, Y and Y' are the elements that make up Q, Y is N, O or S, and Y' is an element of Q adjacent to Y and is N or C.
10. The method for preparing the polyethylene resin composition according to claim 9, wherein: The Ziegler-Natta catalyst is a magnesium-supported titanium catalyst.
11. The method for preparing the polyethylene resin composition according to claim 9, wherein: The Ziegler-Natta catalyst also comprises a halogenated hydrocarbon.
12. The method for preparing the polyethylene resin composition according to claim 9, wherein: The primary polymerization reaction in the first step is carried out while introducing hydrogen in an amount of 0.001 wt % to 0.5 wt % based on the total weight of ethylene added to the first reactor.
13. The method for preparing the polyethylene resin composition according to claim 9, wherein: The metallocene compound represented by Chemical Formula 1 is a compound represented by any one of the following chemical formulas:
14. The method for preparing the polyethylene resin composition according to claim 9, wherein: In the second step, the C4-C8 α-olefin monomer is added in an amount of 0.1 to 10 parts by weight based on 100 parts by weight of the ethylene monomer.
15. The method for preparing the polyethylene resin composition according to claim 9, wherein: The polymerization reaction in the second step is carried out while introducing hydrogen in an amount of 0.0001 wt % to 0.05 wt % based on the total weight of monomers including the ethylene monomer and the C4-C8 α-olefin monomer.
16. A film comprising the polyethylene resin composition of claim 1.
17. The film according to claim 16, wherein The film satisfies the following conditions (e1) to (e3): (e1) when measured according to ASTM D638 at a thickness of 2 mm, the tensile strength in the MD direction is 100 MPa or more, and the tensile strength in the TD direction is 170 MPa or more; (e2) a 1% secant modulus in the MD direction of 800 MPa to 1400 MPa and a 1% secant modulus in the TD direction of 1100 MPa to 2300 MPa when measured according to ASTM D882 at a thickness of 2 mm; (e3) When the film is stretched at a stretching ratio of 5×8 (MD×TD) or more and has a thickness of 20 μm, the haze measured in accordance with ISO 13468 is 30% or less.
Citation Information
Patent Citations
Method, device, and computer program to provide body effect for video call
KR1020230063112A
Sidewall crimping device
KR1020240044221A